Iron nitride permanent magnet and technique for forming iron nitride permanent magnet

By using Fe16N2 material and magnetic domain wall pinning technology, the high cost and supply problems of rare earth elements in existing permanent magnets are solved, and high energy inventory and low cost permanent magnet materials are achieved.

CN119541978APending Publication Date: 2025-02-28REGENTS OF THE UNIVERSITY OF MINNESOTA
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411727741.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2013-02-07
Filing Date
2014-02-06
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Existing permanent magnets often contain rare earth elements, resulting in high material costs and shortage of supply, and complex manufacturing processes and high manufacturing costs.

Method used

Fe16N2 is used as the main magnetic material of the permanent magnet, and block Fe16N2 permanent magnet is formed through steps such as ion implantation, pre-annealing and post-annealing, and non-magnetic elements or molecules are introduced into the material to form the magnetic domain wall pinning site.

Benefits of technology

A permanent magnet with high energy production can be achieved, with energy production reaching 134MGOe, close to or exceeding twice that of NdFeB magnets, and low material cost, making the production process relatively simplified.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

The invention relates to an iron nitride permanent magnet and a technique for forming an iron nitride permanent magnet. Specifically, a bulk permanent magnet material may include from about 5 volume% to about 40 volume% Fe16N2 phase domains, a plurality of non-magnetic atoms or molecules forming domain wall pinning sites, and a remainder of a soft magnetic material wherein at least some of the soft magnetic material is magnetically coupled to the Fe16N2 phase domains by exchange spring coupling. In some examples, a bulk permanent magnet material may be formed by implanting N + ions into an iron workpiece using ion implantation to form an iron nitride workpiece, pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate, and post-annealing the iron nitride workpiece to form Fe16N2 phase domains within the iron nitride workpiece.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a further divisional application of a divisional application with an application date of February 6, 2014, a divisional filing date of September 25, 2020, an application number of 202011023115.4, and an invention name of “Iron Nitride Permanent Magnet and Technology for Forming Iron Nitride Permanent Magnet”; the divisional application with application number 202011023115.4 is a divisional application with application number 201711286395.6, a divisional filing date of December 2017, The invention is a further divisional application of the divisional application with application number 201711286395.6, filed on February 7, 2014, and application date on February 6, 2014, and invention name “Iron nitride permanent magnet and technology for forming iron nitride permanent magnet”; among them, the divisional application with application number 201711286395.6 is a divisional application of the invention patent application with application number 201480019465.X, application date on February 6, 2014, and invention name “Iron nitride permanent magnet and technology for forming iron nitride permanent magnet”. Technical Field

[0002] The present disclosure relates to permanent magnetic materials and techniques for forming permanent magnetic materials. Background Art

[0003] Permanent magnets play a role in many electromechanical systems, including, for example, alternative energy systems. For example, permanent magnets are used in motors or generators, which can be used in vehicles, wind turbines, and other alternative energy mechanisms. Many permanent magnets currently used include rare earth elements, such as neodymium, which can produce a high energy product. The supply of these rare earth elements is relatively short, and they may face higher prices and / or supply shortages in the future. In addition, some permanent magnets including rare earth elements are expensive to manufacture. For example, the manufacture of NdFeB magnets generally includes finely crushed materials, compression of the materials, and sintering at temperatures above 1000°C, all of which contribute to the high manufacturing cost of the magnets. Summary of the invention

[0004] The present disclosure describes a method comprising 16 N2 bulk permanent magnet and for forming Fe 16 N2 bulk permanent magnet technology. Bulk Fe 16 N2 permanent magnets can provide an alternative to permanent magnets including rare earth elements because Fe 16 N2 has a high saturation magnetization constant and magnetic anisotropy constant. The high saturation magnetization constant and magnetic anisotropy constant produce a higher magnetic energy product than rare earth magnets. For example, from thin film Fe 16 Experimental evidence collected using N2 permanent magnets indicates that bulk Fe 16N2 permanent magnets can have desirable magnetic properties, including an energy product of up to about 134 MegaGauss*Oersted (MGOe), which is about twice the energy product of NdFeB (which has an energy product of about 60 MGOe). In addition, iron and nitrogen are abundant elements and are therefore relatively cheap and readily available. Fe 16 The high energy product of N2 magnets can provide high efficiency in applications such as electric motors, generators, and magnetic resonance imaging (MRI) magnets.

[0005] As used herein, bulk material may include a smallest dimension (eg, height, width, or length) greater than about 100 nanometers (nm). In some examples, bulk material may include a smallest dimension greater than about 1 micrometer (μm) or greater than about 100 μm.

[0006] In one aspect, the present disclosure describes a bulk permanent magnetic material comprising from about 5 volume % to about 40 volume % Fe 16 N2 phase magnetic domain; a plurality of non-magnetic atoms or molecules forming a magnetic domain wall pinning site; and a balance of soft magnetic material, wherein at least some of the soft magnetic material is magnetically coupled to the Fe phase magnetic domain by exchange-spring coupling. 16 N2 phase magnetic domain.

[0007] In another aspect, the present disclosure describes a method comprising: implanting N+ ions into an iron workpiece using ion implantation to form an iron nitride workpiece; pre-annealing the iron nitride workpiece to attach the iron nitride to a substrate; and post-annealing the iron nitride workpiece to form Fe in the iron nitride workpiece. 16 N2 phase magnetic domain.

[0008] In another aspect, the present disclosure describes a method comprising: forming a plurality of workpieces comprising an iron nitride material, each of the plurality of workpieces comprising about 5 volume % to about 40 volume % Fe 16 N2 phase magnetic domains; introducing additional iron or non-magnetic material between the plurality of workpieces or into at least one of the plurality of iron nitride material workpieces; and sintering the plurality of iron nitride workpieces together to form a bulk magnet comprising a magnet having about 5 volume % to about 40 volume % Fe 16 Iron nitride of N2 phase magnetic domains.

[0009] In a further aspect, the present disclosure describes a method comprising: forming a plurality of textured iron nitride workpieces by implanting N+ ions into the textured iron workpieces using ion implantation to form textured iron nitride workpieces containing about 8 atomic % to about 15 atomic % N+ ions; and post-annealing the textured iron nitride workpieces to form a Fe volume fraction of about 5 volume % to about 40 volume % in the textured iron nitride workpieces. 16 N2 phase magnetic domain, the remainder is a soft magnetic material including Fe8N, wherein the Fe 16 At least some of the N2 phase magnetic domains are magnetically coupled to at least one of the Fe8N magnetic domains through exchange spring coupling. According to this aspect of the present disclosure, the method further includes: introducing a non-magnetic material between a first workpiece of the plurality of workpieces and a second workpiece of the plurality of workpieces or into at least one of the plurality of iron nitride workpieces, and sintering the plurality of iron nitride workpieces together to form a Fe8N magnetic domain having about 5 volume % to about 40 volume % Fe8N. 16 A bulk magnet of iron nitride with N2 phase magnetic domains, wherein the non-magnetic material forms a magnetic domain wall pinning site in the bulk magnet.

[0010] In another aspect, the present disclosure describes a method comprising: forming a plurality of textured iron nitride workpieces by mixing nitrogen in molten iron such that a concentration of nitrogen atoms in the molten iron is about 8 atomic % to 15 atomic %; rapidly tape casting the molten iron to form the textured iron nitride workpieces; and post annealing the textured iron nitride workpieces to form a Fe nitride volume fraction of about 5 volume % to about 40 volume % in the textured iron nitride workpieces. 16 N2 phase magnetic domain, the remainder is a soft magnetic material including Fe8N, wherein the Fe 16 At least some of the N2 phase magnetic domains are magnetically coupled to at least one of the Fe8N magnetic domains through exchange spring coupling. According to this aspect of the present disclosure, the method further includes: introducing a non-magnetic material between a first workpiece of the plurality of workpieces and a second workpiece of the plurality of workpieces or into at least one of the plurality of iron nitride workpieces, and sintering the plurality of iron nitride workpieces together to form a composite material having about 5 volume % to about 40 volume % of Fe 16 A bulk magnet of iron nitride with N2 phase magnetic domains, wherein the non-magnetic material forms a magnetic domain wall pinning site in the bulk magnet.

[0011] In a further aspect, the present disclosure describes a method comprising: forming a plurality of workpieces of iron nitride material, each of the plurality of workpieces comprising about 5 volume % to about 40 volume % Fe 16N2 phase magnetic domain; introducing a plurality of non-magnetic atoms or molecules between the plurality of workpieces or into at least one of the plurality of iron nitride material workpieces; and sintering the plurality of iron nitride workpieces together to form a composite material including about 5 volume % to about 40 volume % Fe 16 The iron nitride of the N2 phase magnetic domain, the plurality of non-magnetic atoms or molecules forming the magnetic domain wall pinning site, and the bulk permanent magnetic material of the remainder soft magnetic material, wherein at least some of the soft magnetic material is magnetically coupled to the Fe by exchange spring coupling. 16 N2 phase magnetic domain.

[0012] The details of one or more examples are set forth in the accompanying drawings and the description below. Other features, objects, and advantages of the disclosure will be apparent from the description and drawings, and from the claims. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 To illustrate the use of ion implantation to form a 16 Flowchart of an example technology for a permanent magnet with N2 magnetic hard domains and Fe8N magnetic soft domains.

[0014] Figure 2 To show the implantation depth of N+ ions in iron (in angstroms) ) and the implant energy (in kiloelectronvolts (keV)).

[0015] Figure 3 Phase diagram of iron nitride.

[0016] Figure 4 : is a scatter plot showing the relationship between the natural logarithm (natural log) of the diffusion coefficient and the inverse of the temperature.

[0017] Figure 5 A conceptual diagram showing eight (8) iron unit cells in a strained state with nitrogen atoms implanted in the interstitial spaces between the iron atoms.

[0018] Figure 6 To show the Fe8N domain and Fe 16 Conceptual diagram of the material with N2 magnetic domains.

[0019] Figure 7 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains.

[0020] Fig. 8A and Figure 8B To illustrate the use of Fe in a magnetic field including exchange spring coupling with Fe8N magnetic soft domains 16Conceptual diagram of the technique for introducing impurities between workpieces of N2 magnetically hard domain material.

[0021] Fig. 9 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains.

[0022] Fig.10 is a conceptual diagram illustrating an example apparatus for rapid strip casting to texturize an example iron workpiece.

[0023] Fig.11 A conceptual diagram illustrating another example apparatus that may be used to strain an iron workpiece.

[0024] Fig.12 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains.

[0025] Fig.13 is a conceptual diagram illustrating an example apparatus for rapid tape casting to texturize an example iron nitride workpiece.

[0026] Fig.14 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains.

[0027] Fig.15 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains.

[0028] Fig.16 A conceptual diagram illustrating an example apparatus that may strain an iron workpiece and expose it to nitrogen.

[0029] Fig.17 Shows Fig.16 Further details of an example of a crucible heating platform are shown in FIG.

[0030] Fig.18 is a schematic diagram showing an example apparatus that may be used to nitridate an iron workpiece via a urea diffusion process.

[0031] Fig.19 FIG. 5 is a line graph showing Auger measurements of N+ ion concentration as a function of depth in an iron foil after ion implantation and before annealing the iron nitride foil.

[0032] Fig. 20 FIG. 4 is a scatter plot showing the variation of nitrogen concentration with depth in iron foil after post-annealing at different nitrogen fluencies.

[0033] Fig.21A and Fig.21B Magnetic hysteresis loop of magnetization versus coercive force for an example of an iron nitride flake prepared by ion implantation.

[0034] Fig. 22 is a line graph showing an example of the depth distribution of nitrogen in an iron foil before annealing.

[0035] Fig.23 The figure is a scatter plot showing the variation of nitrogen concentration with depth in iron foil after annealing at different nitrogen fluencies.

[0036] Fig.24 The following are x-ray diffraction (XRD) patterns of examples of iron nitride foil before and after annealing.

[0037] Fig.25 Magnetic hysteresis loop of magnetization-coercivity for an example of an iron nitride foil prepared using ion implantation.

[0038] Fig.26 Included are two line graphs showing nitrogen binding energy before and after annealing.

[0039] Figure 27 to Figure 29 Shown are XRD patterns collected from iron nitride samples strained to different levels during post-annealing treatment.

[0040] Figure 30 to Figure 32 Magnetic hysteresis loops of magnetization-coercivity for examples of iron nitride wires exposed to different strains during annealing.

[0041] Fig.33 An example infrared image showing an iron foil directly bonded to a (111) Si substrate.

[0042] Fig.34 A graph showing an example nitrogen depth profile of an ion implanted sample prior to two-step annealing, obtained by Auger electron spectroscopy (AES) with Ar + Measured as a source of deep milling.

[0043] Fig.35 is a graph showing an example nitrogen depth profile after a two-step anneal.

[0044] Fig.36 Graphs showing example XRD patterns of foil samples with different nitrogen fluency on Si(111) substrate after post annealing.

[0045] Fig.37 For illustration, 1×10 17 / cm 2 Plot of example hysteresis loops at different stages for samples prepared with fluence.

[0046] Fig.38 For illustration, 5×10 17 / cm 2 Plot of example hysteresis loops of a fluence-prepared sample after post-annealing.

[0047] Fig.39 To show that to obtain Fig.38 The results shown in Figure 5 are a diagram of the calculated energy products of the tested membranes.

[0048] Fig.40 To obtain Fig.38 and Fig.39 Results are shown in high resolution transmission electron microscopy (HRTEM) images of examples of the tested membranes.

[0049] Fig.41 is shown to obtain Fig.40 The results shown in Figure 5 are example images of x-ray diffraction patterns of the tested samples. DETAILED DESCRIPTION

[0050] The present disclosure describes a method comprising 16 Permanent magnets of N2 phase magnetic domains and for forming a material including Fe 16 In particular, the techniques described herein are used to form permanent magnets comprising Fe 16 N2 phase magnetic domain block permanent magnet. In some examples, Fe 16 N2 phase domains can coexist with other phases, such as phases of soft magnetic materials. 16 The N2 phase can be magnetically coupled to the soft magnetic material through exchange spring coupling, which can effectively harden the soft magnetic material and provide a better connection between the bulk material and the Fe 16 The present disclosure also describes a method for producing a bulk material comprising a single Fe 16 N2 phase or Fe combined with other materials 16 N2 phase block magnet technology.

[0051] Including Fe 16 N2 phase magnets can provide relatively high energy products, for example, when Fe 16 When N2 permanent magnet is anisotropic, it is as high as about 134MGOe. 16In the case where the N2 magnet is isotropic, the energy product can be as high as about 33.5 MGOe. The energy product of permanent magnetism is proportional to the residual coercivity and the residual magnetization. For comparison, Nd2Fe 14 The energy product of a B permanent magnet can be as high as about 60 MGOe. A higher energy product can result in increased efficiency of the permanent magnet when used in motors, generators, etc.

[0052] In addition, Fe 16 The N2 phase permanent magnet may not include rare earth elements, which can reduce the material cost of the magnet and reduce the environmental impact of producing the magnet. In some instances, the use of the techniques described herein can also reduce the environmental impact of producing permanent magnets compared to processes used to prepare rare earth magnets because the techniques may not include the use of a powder phase or a high temperature sintering step.

[0053] However, Fe 16 N2 is a metastable phase that competes with other stable phases of Fe-N. Therefore, it may be difficult to form Fe 16 The bulk material of N2. The Fe 16 The magnetic material of the N2 phase magnetic domain is formed by the Fe 16 N2 magnetic domains and other soft magnetic material magnetic domains to overcome this difficulty. 16 The N2 domains couple to the soft magnetic material through exchange spring coupling and effectively harden the soft magnetic material. In order to achieve exchange spring coupling throughout the volume of the magnetic material, the Fe 16 The N2 magnetic domains are distributed throughout the magnetic material, for example, on a nanometer or micrometer scale.

[0054] As described herein, including Fe 16 The magnetic material of the N2 domains and other soft magnetic material domains may include Fe in a volume fraction of less than about 40 volume percent (vol %). 16 N2 magnetic domain. For example, hard magnetic Fe 16 The N2 phase may constitute about 5% to about 40% by volume of the total volume of the magnetic material, or about 5% to about 20% by volume of the total volume of the magnetic material, or about 10% to about 20% by volume of the total volume of the magnetic material, or about 10% to about 15% by volume of the total volume of the magnetic material, or about 10% to about 10% by volume of the total volume of the magnetic material, with the remainder of the volume being soft magnetic material. The soft magnetic material may include, for example, Fe, FeCo, Fe8N, or a combination thereof.

[0055] In some instances, such as when the soft magnetic material includes Fe or Fe8N, Fe 16The crystallographic texture of the N2 domains and the Fe or Fe8N domains can be coherent. In other words, there can be lattice matching between the domains, including oriented magnetic easy axes. This can promote the hard magnetic Fe 16 Effective exchange spring coupling between N2 domains and soft Fe or Fe8N domains, especially across phase boundaries.

[0056] In some examples, the magnetic material may be a bulk magnetic material. As used herein, the phrases "bulk magnetic material" and "bulk permanent magnetic material" refer to magnetic materials and permanent magnetic materials whose smallest dimension (e.g., length, height, or width) is greater than about 100 nm. In other examples, "bulk magnetic material" and "bulk permanent magnetic material" may have a smallest dimension (e.g., length, height, or width) greater than about 1 μm or greater than about 100 μm.

[0057] The magnetic materials described herein can have a relatively large energy product, such as greater than about 10 MGOe. In some examples, the magnetic materials described herein can have an energy product greater than about 30 MGOe, greater than about 60 MGOe, between about 60 MGOe and about 135 MGOe, greater than about 65 MGOe, or greater than about 100 MGOe. This can be achieved by including an exchange spring coupled to the magnetically soft domains of Fe 16 The N2 phase magnetic domain is realized, and the Fe 16 The N2 phase magnetic domains are alone or in combination with doping elements (eg, atoms) or compounds (eg, molecules) that form magnetic domain wall pinning sites in the magnetic material.

[0058] The present disclosure also describes methods for forming a catalyst comprising Fe 16 Various methods for producing bulk permanent magnets with N2 domains. In some examples, the technique can include using ion implantation to implant N+ ions into a crystallographically textured iron workpiece. In other examples, N+ ions can be introduced into liquid Fe by reactants such as ammonia, ammonium azide, or urea, followed by casting to form a textured workpiece including iron and nitrogen ions.

[0059] Regardless of the formation method, the workpiece including iron and nitrogen ions may be annealed to form Fe in the Fe8N phase. 16 The annealing may be performed at a relatively low temperature (e.g., about 150°C to about 250°C or less than about 214°C) for about 5 hours to about 100 hours to form Fe in the Fe8N phase. 16During the annealing process, the iron nitride material may be strained to promote the transformation of body-centered cubic (bcc) iron crystals to body-centered tetragonal (bct) iron nitride crystals.

[0060] In some cases, Fe can be used with or without the introduction of soft magnetic or nonmagnetic doping materials. 16 Multiple workpieces of N2+Fe8N material are combined and pressed together to form a block permanent magnet. Soft magnetic or non-magnetic material can be provided as the workpiece of the material, and ion implantation is used to implant Fe 16 N2+Fe8N material workpiece, or using cluster implantation to implant Fe 16 In a workpiece of N2+Fe8N material. Soft magnetic or non-magnetic materials can generate magnetic domain wall pinning sites in the material, which can increase the magnetic coercivity of the material.

[0061] Figure 1 To illustrate the use of ion implantation to form a 16 Flowchart of an example technology for a permanent magnet with N2 magnetic hard domains and Fe8N magnetic soft domains. Figure 1 The technique shown is a method for forming a 16 The technique of permanently magnetically forming N2 magnetic hard domains and Fe8N magnetic soft domains can be used alone or in combination with other processing steps to form Fe8N that is exchange coupled with a soft magnetic material such as Fe8N. 16 N2-based bulk permanent magnets. For example, Figure 1 The techniques shown in can be used with Fig. 9 and Fig.13 The other processing steps shown in FIG. 1 are combined to form a bulk magnetic material.

[0062] Figure 1 The technique shown in 1 includes using ion implantation (12) to implant N+ ions into an iron workpiece. The iron workpiece may include a plurality of iron crystals. In some instances, the plurality of iron crystals may have crystal axes oriented in substantially the same direction. For example, a major surface of the iron workpiece may be parallel to the (110) surfaces of all or substantially all of the iron crystals. In other instances, a major surface of the iron workpiece may be parallel to another surface of all or substantially all of the iron crystals. By using a workpiece in which all or substantially all of the iron crystals have substantially aligned crystal axes, the Fe8N phase and the Fe4+ phase may be formed. 16 The anisotropy formed in the N2 phase can be substantially aligned.

[0063] In some instances, a workpiece includes a dimension that is longer than (e.g., much longer than) other dimensions of the workpiece. Example workpieces with a dimension longer than other dimensions include fibers, silk, filaments, cables, films, thick films, foils, strips, sheets, etc. In other instances, the workpiece may not have a dimension longer than other dimensions of the workpiece. For example, the workpiece may include particles or powders, such as spheres, cylinders, flecks, flakes, regular polyhedrons, irregular polyhedrons, and any combination thereof. Examples of suitable regular polyhedrons include tetrahedrons, hexahedrons, octahedrons, decahedrons, dodecahedrons, etc., and their non-limiting examples include cubes, prisms, pyramids, etc.

[0064] exist Figure 1 In some examples of the technology, the workpiece includes a foil. The workpiece can be defined with a thickness on the order of about a few hundred nanometers to a few millimeters. In some examples, all iron workpieces can be defined with a thickness of about 500 nanometers (nm) to about 1 millimeter (mm). The thickness of the iron workpiece can affect the parameters used for ion implantation and annealing of the workpiece, as will be described below. The thickness of the workpiece can be measured in a direction substantially perpendicular to the surface of the substrate to which the workpiece is attached.

[0065] Prior to implanting N+ ions into the iron workpiece, the iron workpiece may be placed on the surface of a silicon substrate or a gallium arsenide (GaAs) substrate. In some examples, the iron workpiece may be placed on a (111) surface of a (single crystal) silicon substrate, but any crystal orientation may be used. In some examples, the iron workpiece may be attached to the surface of the substrate at this point.

[0066] The average depth of the N+ ions implanted into the iron workpiece may depend on the energy of the N+ ions after being accelerated. Figure 2 To show the implantation depth of N+ ions in iron (in angstroms) determined using SRIM ("The Stopping and Range of Ions in Matter" software available from James F. Ziegler at www.srim.org). ) and the implant energy (in kiloelectronvolts (keV)). Figure 2 As shown in Figure 2, as the implantation energy increases, the average implantation depth of N+ ions increases. Figure 2 Not shown in FIG. 1 , but for each implantation energy, N+ ions are implanted in the iron workpiece at a depth range of about the average implantation depth.

[0067] The implantation energy used to implant N+ ions can be selected based at least in part on the thickness of the iron workpiece. Without causing too significant damage to the iron workpiece (including the lattice of the iron crystal in the iron workpiece), the implantation energy can also be selected to implant the N+ ions. For example, although a higher implantation energy can allow N+ ions to be implanted at a greater average depth, a higher implantation energy may increase damage to the iron workpiece, including damage to the lattice of the iron crystal caused by the impact of the N+ ions and ablation of some iron atoms. Therefore, in some instances, the implantation energy can be limited to less than about 180keV. In some instances, the incident angle of the implantation can be about zero degrees (e.g., substantially perpendicular to the surface of the iron workpiece). In other instances, the incident angle of the implantation can be adjusted to reduce lattice damage. For example, the incident angle of the implantation can be about 3° to about 7° with the vertical line.

[0068] As an example, when an iron workpiece is defined with a thickness of about 500 nm, an implantation energy of about 100 keV may be used to implant N+ ions into the iron workpiece. An implantation energy of about 100 keV may also be used to implant N+ ions into iron workpieces of other thicknesses. In other examples, different implantation energies may be used for iron workpieces defined with a thickness of about 500 nm, and the same or different implantation energies may be used for workpieces defined with a thickness different from 500 nm.

[0069] In addition, the fluency of the N+ ions can be selected to implant a desired dose of N+ ions in the iron workpiece. In some examples, the fluency of the N+ ions can be selected to implant approximately a stoichiometric amount of N+ ions in the iron workpiece. 16 The stoichiometric ratio of iron to nitrogen in N2 is 8:1. Therefore, the approximate number of iron atoms in the iron workpiece can be determined, and the number of N+ ions equal to about 1 / 8 (12.5%) of the iron atoms can be implanted into the iron workpiece, such as about 8 atomic % to about 15 atomic %. For example, an iron workpiece having a dimension of about 1 cm×1 cm×500 nm may include about 4.23 x 10 18 Therefore, in order to achieve a stoichiometric ratio of iron atoms to N+ ions in the iron workpiece, about 5.28 x 10 17 N+ ions.

[0070] The temperature of the iron workpiece during the ion implantation process may also be controlled. In some examples, the temperature of the iron workpiece may be between about room temperature and about 500°C.

[0071] Once the N+ ions have been implanted into the iron workpiece (12), the iron workpiece may be subjected to a first annealing step (14), which may be referred to as a pre-annealing step. The pre-annealing step may perform a number of functions, including, for example, firmly attaching the iron workpiece to the substrate. As described below, the firm attachment of the iron workpiece to the substrate allows a post-annealing step to generate stress in the iron workpiece, promoting the transformation of the crystalline structure of at least some crystals in the iron workpiece from body-centered cubic (bcc) iron to body-centered tetragonal (bct) iron nitride. In some instances, the pre-annealing step may also activate the implanted N+ ions, repair damage to the crystal lattice caused by the ion implantation process, and / or remove any oxygen from the workpiece. In some instances, the pre-annealing step may be performed at a temperature of about 450°C to about 550°C for about 30 minutes to about 4 hours. As an example, the pre-annealing step may be performed at a temperature of about 500°C for about 30 minutes to about 1 hour.

[0072] In some examples, in addition to heating the iron workpiece and the substrate, the pre-annealing step may include applying an external force of about 0.2 GPa to about 10 GPa between the iron workpiece and the substrate. The external force may assist in bonding the iron workpiece to the substrate.

[0073] The atmosphere in which the pre-annealing step is performed may include, for example, nitrogen, argon and / or hydrogen, such as a mixture of about 4 volume % hydrogen, about 10 volume % nitrogen and about 86 volume % argon. The composition of the atmosphere may assist in removing oxygen from the workpiece and cleaning the surface of the workpiece.

[0074] After the pre-annealing step (14), the iron workpiece including the implanted N+ ions and the substrate may be exposed to a second annealing step (16), which may be referred to as a post-annealing step. The post-annealing step may be performed at a temperature that produces strain in the iron workpiece due to the difference in thermal expansion coefficients of the substrate and the iron workpiece and achieves a Fe 16 N2 phase. In addition, the post-annealing step allows the diffusion of N+ ion iron crystals to form iron nitride, including Fe 16 N2 phase magnetic domains and Fe8N phase magnetic domains. Figure 3 is the iron nitride phase diagram, reproduced from EH Du Marchi Van Voorthuysen et al. Low-Temperature Extension of the Lehrer Diagram and the Iron-Nitrogen Phase Diagram, 33A Metallurgical and Materials Transactions A2593, 2597 (August 2002). Figure 3As shown in , annealing at relatively low temperatures allows part of the disordered Fe8N phase to transform into Fe 16 N2 ordered phase. In some examples, the post-annealing step may be performed at a temperature below about 250°C, such as about 120°C to about 214°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The post-annealing step may be performed in a nitrogen (N2) or argon (Ar) atmosphere or in a vacuum or near vacuum.

[0075] The temperature and duration of the post-annealing step can be selected based on, for example, the size of the sample and the diffusion coefficient of nitrogen atoms in iron at the post-annealing temperature. Based on these factors, the temperature and duration can be selected to provide sufficient time for the nitrogen atoms to diffuse to the locations in the iron workpiece to form Fe 16 N2 crystal domain. Figure 4 A scatter plot showing the relationship between the natural logarithm of the diffusion coefficient and the inverse of temperature. Figure 4 From the relationship shown in , for a given temperature, the natural logarithm of the diffusion coefficient can be determined, and using the diffusion coefficient the diffusion length for a given time can be determined. As an example, at a temperature of 200° C. and an annealing duration of 40 hours, the diffusion length of nitrogen in iron is about 0.5 micrometers (μm).

[0076] In addition, Fe 16 The temperature and duration of the post-annealing step are selected based on the desired volume fraction of N2 phase domains in the iron nitride workpiece. For example, at the selected temperature, a longer post-annealing step may produce a higher volume fraction of Fe 16 N2. Similarly, for a given post-annealing step duration, higher temperatures can produce higher volume fractions of Fe 16 N2. However, for durations above the threshold, the additional volume fraction of Fe 16 N2 can be limited or eliminated because Fe 16 N2 reaches a relatively stable value. For example, at a temperature of about 150°C, after about 20 hours, Fe 16 The volume fraction of N2 reaches a stable value. The duration of the post-annealing step may be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours.

[0077] Fe8N and Fe 16 N2 has a similar body-centered tetragonal (bct) crystal structure. However, in Fe 16 In N2, the nitrogen atoms are arranged in an orderly manner within the iron lattice, while in Fe8N, the nitrogen atoms are randomly distributed within the iron lattice. Figure 5 To show that Fe16 Conceptual diagram of eight (8) iron unit cells in a strained state with nitrogen atoms implanted in the interstitial spaces between iron atoms in the N2 phase. Figure 5 As shown in 16 In the N2 phase, nitrogen atoms are aligned along the (002) crystal plane. Figure 5 As shown in , the iron nitride unit cell is distorted so that along <001> The length of the unit cell of the axis is about 3.14 angstroms And along <010> and <100> The length of the unit cell of the axis is approximately When in a strained state, the iron nitride unit cell can be referred to as a bct unit cell. When the iron nitride unit cell is in a strained state, <001> The axis may be referred to as the c-axis of the unit cell.

[0078] The post-annealing step facilitates the formation of the bct crystal structure, at least in part due to the stress imposed on the iron lattice due to the differential expansion of the substrate and the iron nitride workpiece during the post-annealing step. For example, the thermal expansion coefficient of iron is 11.8 μm / m·K, while the thermal expansion coefficient of silicon is 2.6 μm / m·K. This difference in thermal expansion coefficients produces a compressive stress substantially parallel to the principal plane of the iron workpiece and along the (110) plane on the iron workpiece. <001> The crystallographic direction produces a corresponding tensile force.

[0079] The post-annealing step forms Fe in the Fe8N domains as well as other Fe and / or iron nitride components. 16 N2 phase magnetic domain. Figure 6 To show the Fe8N domain 22 and Fe 16 Conceptual diagram of the material of the N2 domain 24. Because the iron workpiece is structurally at the nanoscale (e.g., the Fe8N domain 22 and the Fe 16 The size of N2 domain 24 is about nanometers, so the hard magnetic Fe 16 The magnetic coupling between the N2 domain 24 and the soft Fe8N domain 22 occurs substantially throughout the iron workpiece. 16 N2 and Fe8N crystals have essentially similar crystal structures, so the material is likely to be naturally crystallographically coherent, meaning that it has aligned easy axes, which would give rise to anisotropy. This could facilitate the 16 Exchange coupling at the phase boundary between N2 and Fe8N.

[0080] Figure 7 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains. Figure 7 It is a general technology, which will be referred to below. Fig. 9 , Fig.12 , Fig.14 and Fig.15 technology to describe Figure 7 Further details of examples of the general technique are provided below.

[0081] Figure 7 The technique includes forming Fe 16 The iron nitride material of the N2 phase magnetic domain (32). Figure 1 As described, a method for forming a 16 The technology of preparing an iron nitride material (or workpiece) in the N2 phase uses ion implantation to implant N+ ions into an iron workpiece, such as an iron foil, followed by one or more (e.g., two) annealing steps. Fig. 9 , Fig.12 , Fig.14 and Fig.15 Describes the inclusion of Fe 16 Other techniques for forming iron nitride materials with N2 phase magnetic domains (32). These techniques may include: forming a textured iron workpiece, such as a textured iron sheet; implanting N+ ions into the textured iron workpiece to form a textured iron nitride workpiece; and annealing the textured iron nitride workpiece to form Fe 16 The technique may also include: forming a textured iron nitride workpiece, such as a textured iron nitride sheet, by mixing nitrogen into molten iron; and annealing the textured iron nitride workpiece to form Fe 16 N2 phase magnetic domains. The technique may also include: forming an iron workpiece, nitriding the strained iron workpiece, and annealing the nitrided iron workpiece.

[0082] Figure 7 The technique shown in also includes introducing additional ferrous or non-magnetic material (34). In some examples, such as reference Fig. 9 and Fig.12 As described above, the additional iron or non-magnetic material can be used as the workpiece of the iron or non-magnetic material and the workpiece including Fe 16 The N2 phase magnetic domains of the iron nitride material are introduced in an interlaced manner. In other embodiments, such as referring to Fig.14 As described, the additional iron or non-magnetic material can be introduced into the Fe 16In the iron nitride material of N2 phase magnetic domain. Examples of non-magnetic elements (e.g., atoms) or compounds (e.g., molecules) that can be used include Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3 or combinations thereof. The iron or non-magnetic material can be introduced as a workpiece of the material. The workpiece or Fe or non-magnetic powder can have a size (e.g., thickness or diameter) ranging from a few nanometers to hundreds of nanometers, and can function as a domain wall pinning site after the pressing process. Those domain wall pinning sites can enhance the coercive force of the permanent magnet.

[0083] Figure 7 The technique shown in further includes sintering the workpiece to form a bulk magnetic material (36). Fig. 8A and Figure 8B An example of sintering a plurality of workpieces together is shown in FIG. 4. For example, a plurality of iron nitride workpieces 42a-42c (which include Fe 16 N2 phase magnetic domains) can be interlaced with multiple workpieces 44a, 44b including iron or non-magnetic materials. Fig. 8A and Figure 8B Three iron nitride workpieces 42a-42c and two workpieces 44a, 44b including iron or non-magnetic material are shown in FIG. 1 , but in other examples, any number of iron nitride workpieces 42a-42c and two workpieces 44a, 44b including iron or non-magnetic material may be used.

[0084] The iron nitride workpieces 42a-42c may be arranged so that each of the iron nitride workpieces 42a-42c has <001> In the example, each of the iron nitride workpieces 42a-42c has <001> The axis is substantially parallel to the long axis of each nitride iron workpiece 42a-42c, and substantially aligning the nitride iron workpieces 42a-42c may include overlaying one of the nitride iron workpieces 42a-42c on another of the nitride iron workpieces 42a-42c. <001> The alignment of the axes can provide the magnet material 46 with uniaxial magnetic anisotropy ( Figure 8B ).

[0085] When the workpiece is Fig. 8A After interleaving as shown in , the workpieces can be pressed together and sintered. The sintering pressure, temperature, and duration can be selected to mechanically bond the workpieces together while maintaining the crystal structure of the iron nitride workpieces 42a-42c (e.g., including Fe 16N2 phase magnetic domain). Therefore, in some examples, the sintering step can be performed at a relatively low temperature. For example, the sintering temperature can be lower than about 250°C, such as about 120°C to about 250°C, about 150°C to about 250°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The sintering pressure can be, for example, about 0.2 gigapascals (GPa) to about 10GPa. The sintering time can be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours. The sintering time, temperature and pressure may be affected by the material in the workpiece 44a, 44b including iron or non-magnetic material. Sintering can be performed in an ambient atmosphere, in a nitrogen atmosphere, in a vacuum, or in another inert atmosphere.

[0086] After sintering the iron nitride workpieces 42a-42c and the two workpieces 44a, 44b including iron or non-magnetic material, a bulk magnetic material 46 may be formed. The bulk magnetic material 46 may include both Fe8N and Fe 16 N2 and the domain wall pinning sites provided by the iron or non-magnetic material. In this way, the bulk magnetic material 46 can have the desired high energy product, which can approach that of pure Fe 16 The magnetic energy product of N2 (about 134MGOe).

[0087] The bulk magnetic material 46 can be dropped into a Figure 7 The invention can be formed by a variety of different techniques within the scope of the general technology described. Examples of these different techniques refer to Fig. 9 , Fig.12 , Fig.14 and Fig.15 Other techniques for forming bulk magnetic material 46 are described and will be apparent based on this disclosure.

[0088] Fig. 9 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains. Fig. 9 The technique includes forming a textured iron workpiece (52). In some examples, the textured iron workpiece may include textured iron sheets 74a and 74b ( Fig.10 ). In other examples, the textured ferrous workpiece can include another workpiece, such as a fiber, a wire, a filament, a cable, a film, a thick film, a foil, a tape, etc. The textured ferrous workpiece can be formed using, for example, tape casting. Fig.10 is a conceptual diagram illustrating an example apparatus 60 for rapid strip casting to texturize an example ferrous workpiece.

[0089] The fast belt casting apparatus 60 may include an ingot chamber 66 containing a molten iron ingot 62 and heated by a heating source 64, such as a heating coil. In some examples, the temperature of the molten iron ingot 62 in the ingot chamber 66 may be greater than about 1800 Kelvin (K; about 1526.85° C.). The pressure of the iron ingot 62 in the ingot chamber 66 may be about 0.06 MPa to about 0.12 MPa.

[0090] The molten iron ingot 62 flows out of the ingot chamber 66 through the nozzle head 68 to form an iron strip 70. The iron strip 70 is fed into the gap area between the surfaces of the first pinch roller 72a and the second pinch roller 72b (collectively referred to as "pinch rollers 72"), which rotate in opposite directions. In some examples, the distance between the nozzle head 68 and the surface of the pinch roller 72 can be about 2 mm to about 10 mm, such as about 4 mm.

[0091] In some examples, the rotation speed of the first pinch roller 72a and the second pinch roller 72b can vary from about 10 revolutions per molecule (rpm) to 1000 rpm, and the rotation speed of the rollers 72 can be approximately the same. In some examples, the pinch rollers 72 are actively cooled, for example, using water cooling, which maintains the surface of the rollers 72 at a temperature lower than the temperature of the iron strip 70 and assists in cooling and casting the iron strip 70. For example, the temperature of the pinch rollers 72 can be maintained between about 300K (about 26.85°C) and about 400K (about 126.85°C). The pressure applied to the iron ingot by the pinch rollers 72 can be about 0.04MPa to about 0.1MPa.

[0092] After the iron strip 70 is pressed by the pinch rollers 72 and cooled, the iron strip 70 forms textured iron sheets 74a and 74b. In some examples, the textured iron sheets 74a and 74b (collectively referred to as "textured iron sheets 74") can form a textured iron strip (whether alone or as a plurality of iron workpieces after pressing) having at least one dimension (e.g., thickness) of about 1 μm to about 10 mm (such as about 5 μm to about 1 mm). Each of the textured iron sheets 74 can include, for example, a (100) or (110) crystal structure. In other words, the major surface of each textured iron sheet 74 can be parallel to the (100) or (110) surfaces of all or substantially all of the iron crystals in the respective textured iron sheets 74. By using the textured iron sheets 74 in which all or substantially all of the iron crystals have substantially aligned crystal axes in subsequent processing steps, in the formation of Fe8N and Fe 16 The anisotropy formed when the N2 phase magnetic domains are formed can be basically aligned in the crystal.

[0093] After forming the textured iron sheets 74 (52), ion implantation may be used to implant N+ ions into each of the textured iron sheets 74 (12). Figure 1The techniques and parameters described above are used to implant N+ ions into the textured iron sheets 74a and / or 74b. For example, the implantation energy for implanting the N+ ions can be selected based at least in part on the size (e.g., thickness) of each of the textured iron sheets 74 into which the N+ ions are implanted, while avoiding causing significant damage to one of the textured iron sheets 74 (including the lattice of the iron crystal of one of the textured iron sheets 74) that is too significant. For example, although a higher implantation energy can allow the N+ ions to be implanted at a higher average depth, the higher implantation energy may increase the damage caused to the textured iron sheet 74, including damage to the lattice of the iron crystal and ablation of some iron atoms due to the impact of the N+ ions. Therefore, in some instances, the implantation energy can be limited to less than about 180 keV, such as about 100 keV.

[0094] In some examples, the incident angle of the implant can be about zero degrees (e.g., substantially perpendicular to the surface of the textured iron sheet 74). In other examples, the incident angle of the implant can be adjusted to reduce lattice damage. For example, the incident angle of the implant can be about 3° to about 7° from the vertical.

[0095] The temperature of the textured iron sheet 74 during the ion implantation process may also be controlled. In some examples, the temperature of the textured iron sheet 74 may be from about room temperature to about 500°C.

[0096] In addition, the fluency of the N+ ions can be selected to implant a desired dose of N+ ions into a corresponding one of the textured iron sheets 74. In some examples, the fluency of the N+ ions can be selected to implant approximately a stoichiometric amount of N+ ions into a corresponding one of the textured iron sheets 74. 16 The stoichiometric ratio of iron to nitrogen in N2 is 8: 1. Therefore, the approximate number of iron atoms in a corresponding one of the textured iron sheets 74 can be determined, and a number of N+ ions equal to about 1 / 8 (12.5%) of the iron atoms can be implanted into the one of the textured iron sheets 74, such as about 8 atomic % to about 15 atomic %.

[0097] Once the selected number of N+ ions have been implanted into the textured iron sheet 74a or 74b to form a textured iron nitride sheet, the textured iron nitride sheet may be annealed to allow the N+ ions to diffuse into suitable locations of the iron crystals to form Fe in the textured iron nitride sheet. 16 N2 phase magnetic domains and Fe8N phase magnetic domains (16). The annealing in this step can be similar to that relative to Figure 1 Post-annealing step as described. Figure 3 As shown, annealing at relatively low temperatures allows part of the disordered Fe8N phase to transform into Fe 16N2 ordered phase. In some examples, the post-annealing step can be performed at a temperature below about 250° C., such as about 120° C. to about 214° C., about 120° C. to about 200° C., about 150° C. to about 200° C., or about 150° C. The post-annealing step can be performed in a nitrogen (N2) or argon (Ar) atmosphere or in a vacuum or near vacuum.

[0098] The temperature and duration of the post-annealing step can be selected based on, for example, the size of the textured iron nitride workpiece (e.g., textured iron nitride sheet) and the diffusion coefficient of nitrogen atoms in iron at the post-annealing temperature. Based on these factors, the temperature and duration can be selected to provide sufficient time for the nitrogen atoms to diffuse to locations in the textured iron nitride workpiece to form Fe 16 N2 magnetic domain.

[0099] In addition, the Fe content of the textured iron nitride workpiece can be determined based on the desired Fe content. 16 The temperature and duration of the post-annealing step are selected based on the volume fraction of N2 phase domains. For example, at a selected temperature, a longer post-annealing step can produce a higher volume fraction of Fe 16 N2. Similarly, for a given post-annealing step duration, higher temperatures can produce higher volume fractions of Fe 16 N2. However, for a duration above the threshold, Fe 16 The additional volume fraction of N2 may be limited or eliminated because Fe 16 The volume fraction of N2 reaches a relatively stable value. The duration of the post-annealing step may be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours.

[0100] During the post-annealing step, the textured iron nitride workpiece may be subjected to strain to promote the conversion of at least some of the bcc iron crystals to the bct crystal structure. Various strain inducing devices may be used to apply strain forces to the textured iron nitride workpiece. For example, a first end of the textured iron nitride workpiece may be received by a first roller (e.g., by winding) and a second end of the textured iron nitride workpiece may be received by a second roller (e.g., by winding). The rollers may rotate in opposite directions to apply a tensile force on the textured iron nitride workpiece.

[0101] In other examples, opposite ends of the textured iron nitride workpiece may be clamped in mechanical clamps (eg, clamps), and the mechanical clamps moved away from each other to apply a tensile force on the textured iron nitride workpiece. Fig.1186a-86d. Once the iron workpiece 90 is secured in the apparatus 80, a bolt 88 may be turned to rotate the threaded body of the bolt 88 and increase the distance between the first clamp 82 and the second clamp 84. The increase in the distance between the clamps 82 and 84 applies a tensile force on the textured iron nitride workpiece 90. The value of the elongation or stress generated by the rotation of the bolt 88 may be measured by any suitable gauge, such as, for example, a strain gauge. In some examples, the apparatus 80 may be placed in a furnace (e.g., a tube furnace) or other heated environment to allow the textured iron nitride workpiece 90 to be heated during and / or after the textured iron nitride workpiece 90 is strained by the apparatus 80.

[0102] The strain inducing device can strain the textured iron nitride workpiece 90 to a certain elongation. For example, the strain on the textured iron nitride workpiece 90 can be about 0.1% to about 7%. In other examples, the strain on the textured iron nitride workpiece 90 can be less than about 0.1% or greater than about 7%. In some examples, applying a certain strain on the textured iron nitride workpiece 90 can produce a substantially similar strain on a single unit cell of the iron crystal so that the unit cell is stretched along the length of the unit cell. <001> The elongation of the shaft is from about 0.1% to about 7%.

[0103] The cross-sectional area of ​​the textured iron nitride workpiece (in a plane substantially orthogonal to the direction in which the iron workpiece is stretched / strained) can affect the amount of force that must be applied to the textured iron nitride workpiece to produce a given strain. 2 Applying a force of about 144 N to a textured iron nitride workpiece having a cross-sectional area of ​​about 0.0314 mm may produce a strain of about 7%. 2 Applying a force of about 576 N to a textured iron nitride workpiece having a cross-sectional area of ​​about 0.0707 mm may produce a strain of about 7%. 2 Applying a force of about 1296 N to a textured iron nitride workpiece having a cross-sectional area of ​​about 0.126 mm may produce a strain of about 7%. 2 Applying a force of about 2304 N to a textured iron nitride workpiece having a cross-sectional area of ​​about 0.196 mm may produce a strain of 7%. 2 The cross-sectional area of ​​the textured iron nitride workpiece can produce a strain of about 7% when a force of about 3600N is applied.

[0104] The post-annealing and straining steps lead to the formation of Fe in the magnetic domains of Fe8N and other Fe and / or Fe nitride compositions. 16 N2 phase domains, for example, Figure 6 Because the textured iron nitride workpiece is nanoscale in structure (e.g., Fe8N domains 22 and Fe 16 N2 magnetic domains 24 are all about nanometers), so the hard magnetic Fe 16 The magnetic coupling between the N2 domains 24 and the soft Fe8N domains 22 can occur substantially throughout the workpiece. 16 N2 and Fe8N crystals have substantially similar crystal structures, so the material may be crystallographically coherent in nature, meaning that it has aligned easy axes, which creates anisotropy. This may facilitate the transfer of Fe 16 Exchange coupling at the phase boundary between N2 and Fe8N.

[0105] Fig. 9 The step of forming a textured iron workpiece (e.g., a textured iron sheet), the step of implanting N+ ions using ion implantation (12), and the annealing step (16) may constitute a step of forming a textured iron workpiece (e.g., a textured iron sheet) 16 Iron nitride material (32) with N2 phase magnetic domain, such as Figure 7 shown. Fig. 9 The technique may also include introducing additional ferrous or non-magnetic material between the iron nitride workpieces (e.g., sheets) (54), which is an example of introducing additional ferrous or non-magnetic material (34), see Figure 7 Description of. Example non-magnetic materials (e.g., atoms) or compounds (e.g., molecules) that can be used include Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3, or combinations thereof.

[0106] The ferrous or non-magnetic material may be introduced as a workpiece or powder of material and may be introduced in a 16 Between the workpiece of the textured iron nitride of the N2 phase magnetic domain. The workpiece of the material or Fe or non-magnetic powder can have a size (e.g., thickness or diameter) ranging from a few nanometers to hundreds of nanometers, and can function as a magnetic domain wall pinning site after the sintering process. Those magnetic domain wall pinning sites can enhance the coercive force of the permanent magnet.

[0107] Fig. 9 The technique may also include sintering the workpiece (eg, sheet) to form a bulk magnetic material (36). Figure 7 , Fig. 8A and Figure 8B As described, the sintering pressure, temperature, and duration may be selected to mechanically bond the workpieces while maintaining the crystal structure of the textured iron nitride workpiece (e.g., also comprising Fe16 N2 phase magnetic domain). Therefore, in some examples, the sintering step can be performed at a relatively low temperature. For example, the sintering temperature can be lower than about 250°C, such as about 120°C to about 250°C, about 150°C to about 250°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The sintering pressure can be, for example, about 0.2GPa to about 10GPa. The sintering time can be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours. The sintering time, temperature and pressure can be affected by the material in the workpiece 44a, 44b including iron or non-magnetic material.

[0108] After sintering the textured iron nitride workpiece with iron or non-magnetic material, a bulk magnetic material (e.g., a bulk permanent magnet) can be formed. The bulk magnetic material can include both Fe8N and Fe 16 N2 and the domain wall pinning sites provided by the ferrous or nonmagnetic material. In this way, bulk magnetic materials can have the desired high energy product, which can approach that of pure Fe 16 Energy product of N2 (about 134MGOe).

[0109] Fig.12 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains. Fig.12 The technique includes forming a textured iron nitride workpiece (eg, a textured iron nitride sheet) (92). The textured iron nitride workpiece may be formed using, for example, tape casting. Fig.13 A conceptual diagram illustrating an example apparatus 100 for rapid tape casting to texturize an example iron nitride workpiece.

[0110] The fast belt casting apparatus 10 may include an ingot chamber 66 containing a molten iron ingot 62 and heated by a heating source 64, such as a heating coil. In some examples, the temperature of the molten iron ingot 62 in the ingot chamber 66 may be greater than about 1800 Kelvin (K; about 1526.85° C.). The pressure of the iron ingot 62 in the ingot chamber 66 may be about 0.06 MPa to about 0.12 MPa.

[0111] The ingot chamber 66 also includes a nitrogen inlet 102 through which a nitrogen source is introduced into the molten iron ingot 62 to form a molten iron nitride mixture 104. The nitrogen may be provided in various forms or from various sources through the nitrogen inlet 102. For example, the nitrogen may be provided in the form of ammonia, ammonium azide, or urea, which may be introduced through the nitrogen inlet 102 and subsequently decompose when mixed with the molten iron to release nitrogen atoms in the molten iron nitride mixture 104.

[0112] In some examples, a nitrogen source may be provided to produce approximately a stoichiometric amount of nitrogen atoms in the iron nitride mixture 104. 16 The stoichiometric ratio of iron to nitrogen in N2 is 8: 1. Therefore, the approximate number of iron atoms in the iron nitride mixture 104 can be determined, and the number of nitrogen atoms equal to about 1 / 8 (12.5%) of the iron atoms, such as about 8 atomic % to about 15 atomic %, can be provided to the iron nitride mixture 104 through the nitrogen inlet 102.

[0113] The molten iron nitride mixture 104 flows out of the ingot chamber 66 through the nozzle head 68 to form the iron nitride ribbon 106. The iron nitride ribbon 106 is fed into the gap area between the surfaces of the first pinch roller 72a and the second pinch roller 72b (collectively referred to as "pinch rollers 72"), which rotate in opposite directions. In some examples, the distance from the nozzle head 68 to the surface of the pinch roller 72 can be about 1 mm to about 50 mm, such as about 4 mm.

[0114] In some examples, the rotation speed of the first and second pinch rollers 72a, 72b can vary from about 10 revolutions per minute (rpm) to 1000 rpm, and the rotation speeds of the rollers 72 can be approximately the same. In some examples, the pinch rollers 72 are actively cooled, such as using water cooling, which maintains the surface of the rollers 72 at a temperature lower than the temperature of the nitrided iron strip 106 and assists in cooling and casting the nitrided iron strip 106. For example, the temperature of the pinch rollers 72 can be maintained at about 300K (about 26.85°C) to about 400K (about 126.85°C). The pressure applied to the nitrided iron strip 106 by the pinch rollers 72 can be about 0.04 MPa to about 0.1 MPa.

[0115] After the iron nitride strip 106 is pressed between the pinch rollers 72 and cooled, the iron nitride strip 106 forms textured iron nitride sheets 108a and 108b. In some examples, the textured iron nitride sheets 108a and 108b (collectively referred to as "textured iron nitride sheets 108") can form a textured iron nitride strip having at least one dimension (e.g., thickness) in the range of about 1 μm to about 10 mm, such as about 5 μm to about 1 cm (whether individually or after pressing a plurality of textured iron nitride sheets 108). Each of the textured iron nitride sheets 108 can include, for example, a (100) or (110) crystal structure. In other words, the major surface of each of the textured iron nitride sheets 108 can be parallel to the (100) or (110) surfaces of all or substantially all of the iron crystals in the corresponding one of the textured iron nitride sheets 108. By using a textured iron nitride sheet 108a or 108b in which all or substantially all of the iron crystals have substantially aligned crystal axes in a subsequent processing step, the Fe8N and Fe 16The anisotropy formed when the N2 phase magnetic domains are basically aligned in the crystal.

[0116] After forming the textured iron nitride sheet 108 (92), the textured iron nitride sheet 108 may be annealed to form Fe 16 N2 phase magnetic domains and Fe8N phase magnetic domains (16). This step may be similar to or substantially the same as with respect to Figure 1 and Fig. 9 Description. For example, the post-annealing step may be performed at a temperature below about 250°C, such as about 120°C to about 214°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The post-annealing step may be performed in a nitrogen (N2) or argon (Ar) atmosphere, or in a vacuum or near vacuum. The duration of the post-annealing step may be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours.

[0117] The temperature and duration of the post-annealing step may be based on, for example, the size of the textured iron nitride workpiece (e.g., a textured iron nitride sheet), the diffusion coefficient of nitrogen atoms in iron at the annealing temperature, and the desired Fe content in the textured iron nitride workpiece. 16 Based on these factors, the temperature and duration can be selected to provide sufficient time for nitrogen atoms to diffuse into the textured iron nitride workpiece to form Fe 16 N2 magnetic domain.

[0118] During the post-annealing step, the textured iron nitride workpiece may be subjected to strain to promote the conversion of at least some of the bcc iron crystals to the bct crystal structure. The strain inducing device may strain the textured iron nitride workpiece to a certain elongation. For example, the strain on the textured iron nitride workpiece may be from about 0.1% to about 7%. In other examples, the strain on the textured iron nitride workpiece may be less than about 0.1% or greater than about 7%. In some examples, applying a certain strain to the textured iron nitride workpiece may produce substantially similar strains on individual unit cells of the iron crystals, such that the unit cells are stretched along the <001> The shaft elongates from about 0.1% to about 7%.

[0119] Fig.12 The steps of forming a textured iron nitride workpiece (eg, sheet) (92) and annealing the textured iron nitride workpiece (16) as shown in the drawings may constitute forming Figure 7 The shown includes Fe 16 Iron nitride material (32) with N2 phase magnetic domain. Fig.12 The technique may also include introducing additional ferrous or non-magnetic material between the iron nitride workpieces (e.g., sheets) (54), which is a reference Figure 7 An example of introducing additional iron or non-magnetic materials (34) is described. Example non-magnetic elements (e.g., atoms) or compounds (e.g., molecules) that can be used can include Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3, or combinations thereof.

[0120] Iron or non-magnetic materials can be introduced as workpieces or powders of materials and can be introduced in 16 The texture of N2 phase magnetic domains between the workpieces of iron nitride. The workpieces of the material or Fe or non-magnetic powder can have a size (e.g., thickness or diameter) ranging from a few nanometers to hundreds of nanometers, and the function of the magnetic domain wall pinning sites can be volatilized after the sintering process. Those magnetic domain wall pinning sites can enhance the coercive force of the permanent magnet.

[0121] Fig.12 The technique may also include sintering the workpiece (eg, sheet) to form a bulk magnetic material (36). Figure 7 , Fig. 8A and Figure 8B As described, the sintering pressure, temperature, and duration may be selected to mechanically bond the workpieces while maintaining the crystal structure of the textured iron nitride workpiece (e.g., as comprising Fe 16 N2 phase magnetic domain). Therefore, in some examples, the sintering step can be performed at a relatively low temperature. For example, the sintering temperature can be lower than about 250°C, such as about 120°C to about 250°C, about 150°C to about 250°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The sintering pressure can be, for example, about 0.2GPa to about 10GPa. The sintering time can be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours. The sintering time, temperature and pressure may be affected by the material in the workpiece 44a, 44b including iron or non-magnetic material.

[0122] After sintering the textured iron nitride workpiece with iron or non-magnetic material, a bulk magnetic material (e.g., a bulk permanent magnet) can be formed. The bulk magnetic material may include both Fe8N and Fe 16 N2 and the domain wall pinning sites provided by the iron or nonmagnetic material. In this way, the bulk magnetic material can have the desired high energy product, which can approach that of pure Fe 16 Energy product of N2 (about 134MGOe).

[0123] Fig.14 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16Flowchart of an example technology for bulk material of N2 magnetically hard domains. Fig.14 The technique is similar to Fig. 9 The technique described above; however, instead of introducing additional iron or non-magnetic material (54) between the iron nitride workpieces (e.g., sheets), Fig.14 Techniques include the use of ion implantation or cluster implantation to dope Fe 16 The textured iron nitride workpiece (108) has N2 phase magnetic domains. Fig.14 Techniques may include, for example, forming the textured iron workpiece (52) using strip casting. Fig.14 The technique may also include implanting N+ ions into the textured iron workpiece using ion implantation (12) to form a textured iron nitride workpiece, and annealing the textured iron nitride workpiece to form Fe 16 N2 phase magnetic domain (16).

[0124] So, Fig.14 Techniques include the use of ion implantation or cluster implantation to dope Fe 16 A textured iron nitride workpiece (108) having N2 phase magnetic domains. Example non-magnetic elements (e.g., atoms) or compounds (e.g., molecules) that can be used to dope the textured iron nitride workpiece include Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3, or combinations thereof. By doping these elements or compounds into the textured iron nitride workpiece, magnetic domain wall pinning can be improved compared to examples where particles or workpieces of these materials are interleaved with the textured iron nitride workpiece prior to sintering the workpieces together. Improving magnetic domain wall pinning can improve the magnetic properties of the final bulk magnetic material, including the coercivity of the bulk magnetic material.

[0125] Fig.14 The technique further includes sintering the doped textured iron nitride workpiece to form a bulk magnetic material (36). Figure 7 , Fig. 8A and Figure 8B As described, the sintering pressure, temperature, and duration may be selected to mechanically bond the workpieces while maintaining the crystal structure of the textured iron nitride workpiece (e.g., as comprising Fe 16N2 phase magnetic domain). Therefore, in some examples, the sintering step can be performed at a relatively low temperature. For example, the sintering temperature can be lower than about 250°C, such as about 120°C to about 250°C, about 150°C to about 250°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The sintering pressure can be, for example, about 0.2GPa to about 10GPa. The sintering time can be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours. The sintering time, temperature and pressure may be affected by the material in the workpiece 44a, 44b including iron or non-magnetic material.

[0126] After sintering the textured iron nitride workpiece with iron or non-magnetic material, a bulk magnetic material (e.g., a bulk permanent magnet) can be formed. The bulk magnetic material can include both Fe8N and Fe 16 N2 and the domain wall pinning sites provided by the iron or nonmagnetic material. In this way, the bulk magnetic material can have the desired high energy product, which can approach that of pure Fe 16 Energy product of N2 (about 134MGOe).

[0127] Fig.15 To illustrate the formation of a Fe8N magnetic soft domain exchange spring coupling with a magnetic domain wall pinning site, 16 Flowchart of an example technology for bulk material of N2 magnetically hard domains. Fig.15 The technology will also refer to Fig.16 and Fig.17 to describe. Fig.16 A conceptual diagram illustrating an example apparatus that may strain an iron workpiece and expose it to nitrogen. Fig.17 Shows Fig.16 Further details of an example of a cold crucible heating platform are shown in FIG.

[0128] Fig.16 The example apparatus includes a first roller 122, a second roller 124, and a crucible heating platform 126. The first roller 122 and the second roller 124 are configured to receive a first end 138 and a second end 140 of an iron workpiece 128, respectively. The iron workpiece 128 defines a long axis between the first end 138 and the second end 140. Fig.17 As seen in FIG. 1 , an iron workpiece 128 passes through an aperture 130 defined by the crucible heating platform 126 . The crucible heating platform 126 includes an induction coil 132 that surrounds at least a portion of the aperture 130 defined by the crucible heating platform 126 .

[0129] Fig.15An example technique includes moving the iron workpiece 128 along a substantially parallel (eg, parallel or nearly parallel) axis of at least one iron crystal in the iron workpiece 128. <001> The direction of the axis of deformation affects the ferrous workpiece 128 (112). In some examples, the ferrous workpiece 128 formed of iron has a body-centered cubic (bcc) crystal structure.

[0130] In some examples, the iron workpiece 128 is formed of a single bcc crystal structure. In other examples, the iron workpiece 128 may be formed of a plurality of bcc iron crystals. In some of these examples, the plurality of iron crystals are oriented so that at least some (e.g., most or substantially all) of the individual unit cells and / or crystals are oriented in a manner that is consistent with the embodiment of the present invention. <001> The axis is substantially parallel to the direction in which the strain is applied to the iron workpiece 128. For example, when iron is formed into the iron workpiece 128, at least some <001> The axis may be substantially parallel to the long axis of the ferrous workpiece 128, such as Fig.16 and Fig.17 In some examples, the single crystal iron nitride workpiece can be formed using a crucible technique. In addition to this crucible technique, the single crystal iron workpiece can be formed by floating through a micro-melting zone or pulling from a micro-shaper to form the iron workpiece 128.

[0131] In some examples, the iron workpiece 128 may have a crystalline texture. Techniques that may be used to form a crystal-textured (eg, having a desired crystal orientation along a certain direction of the workpiece) iron workpiece include those described with reference to Fig. 9 and Fig.10 Rapid strip casting as described.

[0132] A variety of strain inducing devices may be used to impart strain to the ferrous workpiece 128. For example, Fig.16 As shown, the first end 138 and the second end 140 of the ferrous workpiece 128 may be received (eg, wound) by the first roller 122 and the second roller 124, respectively, and the rollers 122, 124 may be rotated in opposite directions (eg, by Fig.16 134 and 135 in the figure) to apply a tensile force on the iron workpiece 128. In other examples, the opposite ends of the iron workpiece 128 can be clamped in mechanical clamps (e.g., clamps), and the mechanical clamps are moved away from each other to apply a tensile force on the iron workpiece 128, as described above with reference to Fig.11 as described.

[0133] The strain inducing device can stress the iron workpiece 128 to a certain elongation. For example, the strain on the iron workpiece 128 can be about 0.1% to about 7%. In other examples, the strain on the iron workpiece 128 can be less than about 0.1% or greater than about 7%. In some examples, applying a certain strain on the iron workpiece 128 can produce a substantially similar strain on a single unit cell of iron, causing the unit cell to be stretched along the <001> The shaft elongates from about 0.1% to about 7%.

[0134] The size of the iron workpiece (such as, for example, the diameter of the iron wire or the cross-sectional area of ​​the iron sheet (a plane substantially orthogonal to the direction in which the iron sheet is stretched / strained)) can affect the amount of force that must be applied to the iron workpiece 128 to produce a given strain. For example, applying a force of about 144N to an iron wire having a diameter of about 0.1mm can produce a strain of about 7%. As another example, applying a force of about 576N to an iron wire having a diameter of about 0.2mm can produce a strain of about 7%. As another example, applying a force of about 1296N to an iron wire having a diameter of about 0.3mm can produce a strain of about 7%. As another example, applying a force of about 2304N to an iron wire having a diameter of about 0.4mm can produce a strain of about 7%. As another example, applying a force of about 3600N to an iron wire having a diameter of about 0.5mm can produce a strain of about 7%.

[0135] In some examples, the iron workpiece 128 may include doping elements once the F e16 N2 phase composition, which is used to stabilize Fe 16 N2 phase composition. For example, the phase-stabilizing doping elements may include cobalt (Co), titanium (Ti), copper (Cu), zinc (Zn), etc.

[0136] While the strain inducing device applies the strain to the iron workpiece 128 and / or once the strain inducing device applies the substantially constant strain to the iron workpiece 128, the iron workpiece 128 can be nitrided (114). In some examples, during the nitriding process, the iron workpiece 128 can be heated using a heating device. An example of a heating device that can be used to heat the iron workpiece 128 is a crucible heating platform 126, such as Fig.16 and Fig.17 shown.

[0137] The crucible heating platform 126 defines an aperture 130 through which the ferrous workpiece 128 passes (e.g., a portion of the ferrous workpiece 128 is disposed). In some examples, no portion of the crucible heating platform 126 contacts the ferrous workpiece 128 during heating of the ferrous workpiece 128. In some embodiments, this is advantageous because it reduces the contact and diffusion of unwanted elements or chemical species into the ferrous workpiece 128. Unwanted elements or chemical species may affect the properties of the ferrous workpiece 128; therefore, it may be desirable to reduce or limit contact between the ferrous workpiece 128 and other materials.

[0138] The crucible heating platform 126 also includes at least a portion surrounding an aperture 130 defined by the crucible heating platform 126. The induction coil 132 includes a conductive material, such as aluminum, silver, or copper, through which an electric current can flow. The electric current can be an alternating current (AC), which can induce eddy currents in the iron workpiece 128 and heat the iron workpiece 128. In other examples, instead of using the crucible heating platform 126 to heat the iron workpiece 128, other non-contact heating sources can be used. For example, a radiant heat source (such as an infrared heating lamp) can be used to heat the iron workpiece 128. As another example, a plasma arc lamp can be used to heat the iron workpiece 128.

[0139] Regardless of the heating device used to heat the ferrous workpiece 128 during the nitriding process, the heating device can heat the ferrous workpiece 128 to a temperature and for a time sufficient to allow the nitrogen to diffuse substantially throughout the thickness, diameter, or internal volume of the ferrous workpiece 128 to a predetermined concentration. As such, the heating time and temperature are related and can also be affected by the composition and / or geometry of the ferrous workpiece 128. For example, the ferrous workpiece 128 can be heated to a temperature of about 125° C. to about 700° C. for about 2 hours to about 9 hours. In some examples, the ferrous workpiece 128 can be heated to a temperature of about 500° C. to about 660° C. for about 2 hours to about 4 hours.

[0140] In some examples, the iron workpiece 128 includes an iron wire having a diameter of about 0.1 mm. In some of these examples, the iron workpiece 128 may be heated to a temperature of about 125° C. for about 8.85 hours or to a temperature of about 600° C. for about 2.4 hours. In general, at a given temperature, the nitriding treatment time may be inversely proportional to the square of a characteristic dimension of the iron workpiece 128 (such as the diameter of the iron wire or the thickness of the iron sheet).

[0141] In addition to heating the iron workpiece 128, nitriding the iron workpiece 128 (114) includes exposing the iron workpiece 128 to an atomic nitrogen species that diffuses into the iron workpiece 128. In some examples, the atomic nitrogen species can be provided as diatomic nitrogen (N2), which is then separated (fragmented) into individual nitrogen atoms. In other examples, the atomic nitrogen can be provided by another atomic nitrogen precursor, such as ammonia (NH3). In other examples, the atomic nitrogen can be provided by urea (CO(NH2)2) or ammonium azide ((NH4)N3).

[0142] Nitrogen can be provided in a gas phase alone (e.g., substantially pure ammonia, ammonium azide, or urea, or diatomic nitrogen) or as a mixture with a carrier gas. In some examples, the carrier gas is argon (Ar). The gas or gas mixture can be provided at any suitable pressure, such as about 0.001 Torr (about 0.133 Pascals (Pa)) to about 10 Torr (about 1333 Pa), such as about 0.01 Torr (about 1.33 Pa) to about 0.1 Torr (about 13.33 Torr). In some examples, when nitrogen is delivered as part of a mixture with a carrier gas, the partial pressure of nitrogen or a nitrogen precursor (e.g., NH3) can be about 0.02 to about 0.1.

[0143] A nitrogen precursor (e.g., N2 or NH3) may be cracked to form atomic nitrogen species using various techniques. For example, radiation heating may be used to crack the nitrogen precursor to form atomic nitrogen species and / or to promote a reaction between the nitrogen precursor and the iron workpiece 128. As another example, a plasma arc lamp may be used to crack the nitrogen precursor to form atomic nitrogen species and / or to promote a reaction between the nitrogen precursor and the iron workpiece 28.

[0144] In some examples, the iron workpiece 128 can be nitrided (114) by a urea diffusion process, in which urea is used as a nitrogen source (e.g., rather than diatomic nitrogen or ammonia). Urea (also known as carbamide) is an organic compound having the chemical formula CO(NH2)2 that can be used as a nitrogen-releasing fertilizer in some circumstances. To nitridate (114) the iron workpiece 128, the urea can be heated, for example, in a furnace with the iron workpiece 128, to generate decomposed nitrogen atoms that can diffuse into the iron workpiece 128. As will be further described below, the composition of the resulting nitrided iron material can be controlled, to some extent, by the temperature of the diffusion process and the ratio (e.g., weight ratio) of iron to urea used in the process. In other examples, the iron workpiece 128 can be nitrided by an implantation method similar to that used to introduce dopants in semiconductor processes.

[0145] Fig.18 A schematic diagram of an example apparatus 164 is shown that can be used to nitride an iron workpiece 128 by a urea diffusion process. For example, when having single crystal iron, multiple crystal structures, or textured structures, this urea diffusion process can be used to nitride the iron workpiece 128. In addition, iron materials of different shapes, such as wires, sheets, or blocks, can also be diffused using this process. For wire materials, the diameter of the wire can vary, for example, from a few microns to a few millimeters. For sheet materials, the thickness of the sheet can be, for example, a few nanometers to a few millimeters. For bulk materials, the material weight can be about 1 mg to several kilograms.

[0146] As shown, the apparatus 164 includes a crucible 166 within a vacuum furnace 168. The iron workpiece 128 is in the crucible 166 along with a nitrogen source urea 172. Fig.18 As shown, a carrier gas including Ar and hydrogen is fed into the crucible 166 during the urea diffusion process. In other examples, a different carrier gas or even no carrier gas may be used. In some examples, the gas flow rate in the vacuum furnace 168 during the urea diffusion process may be about 5 standard cubic meters per minute (sccm) to about 50 sccm, such as, for example, 20 sccm to about 50 sccm or 5 sccm to about 20 sccm.

[0147] The heating coil 170 can heat the iron workpiece 128 and the urea 172 during the urea diffusion process using any suitable technique, such as, for example, eddy current, induction current, radio frequency, etc. The crucible 166 can be configured to withstand the temperatures used during the urea diffusion process. In some examples, the crucible 166 can withstand temperatures up to about 1600°C.

[0148] Urea 172 may be heated with the iron workpiece 128 to generate nitrogen that may diffuse into the iron workpiece 128 to form an iron nitride material. In some examples, urea 172 and the iron workpiece 128 may be heated to about 650° C. or higher in the crucible 166 and then cooled to quench the mixture of iron and nitrogen to form a nitride material having Fe substantially throughout the thickness, diameter, or volume of the iron workpiece 128. 16 Iron nitride material composed of N2 phase. In some examples, urea 172 and iron workpiece 128 can be heated to about 650°C or higher in crucible 166 for about 5 minutes to about 1 hour. In some examples, urea 172 and iron workpiece 128 can be heated to about 1000°C to about 1500°C for several minutes to about 1 hour. The heating time may depend on the thermal coefficient of nitrogen at different temperatures. For example, if the iron workpiece defines a thickness of about 1 micron, the diffusion process is completed in about 5 minutes at about 1200°C, in about 12 minutes at 1100°C, and so on.

[0149] To cool the heated material during the cold shock process, cold water can be circulated outside the crucible to quickly cool the contents. In some examples, the temperature can be reduced from 650°C to room temperature in about 20 seconds.

[0150] As will be described below, in some examples, the temperature of the urea 172 and the iron workpiece 128 may be, for example, about 120° C. to about 250° C. to anneal the iron and nitrogen mixture to form a layer having Fe throughout substantially the entire thickness, diameter, or volume of the iron workpiece 128. 16The nitride iron material of N2 phase composition. Urea 172 and the iron workpiece 128 can be at the annealing temperature, for example, for at least about 1 hour. For example, when the iron material is a single crystal iron workpiece or a textured iron workpiece having at least one dimension at the micron level, such an annealing process can be combined with other nitrogen diffusion techniques or as a substitute for other nitrogen diffusion techniques. In each of the annealing and cold shock, nitrogen can be diffused into the iron workpiece 128 from nitrogen in the furnace 68 or a gas mixture including Ar and hydrogen carrier gas. In some instances, the gas mixture can have a composition of about 86% Ar + 4% H2 + 10% N2. In other instances, the gas mixture can have a composition of 10% N2 + 90% Ar or 100% N2 or 100% Ar.

[0151] As will be further described below, the composition of the iron nitride material formed by the urea diffusion process can depend on the weight ratio of urea to iron used. Likewise, in some examples, the weight ratio of urea to iron can be selected to form a Fe 16 However, this urea diffusion process can be used to form iron nitride materials with 16 Iron nitride materials other than N2 phase composition, such as, for example, Fe2N, Fe3N, Fe4N, Fe8N, etc.

[0152] Regardless of the technique (14) used to nitridize the iron workpiece 128, nitrogen can be diffused into the iron workpiece 128 to a concentration of about 8 atomic percent (atomic %) to about 14 atomic %, such as about 11 atomic %. The concentration of nitrogen in the iron can be an average concentration and can vary throughout the iron workpiece 128. In some examples, the phase composition of at least a portion of the resulting nitrided iron workpiece 128 (after nitriding the iron workpiece 128 (114)) can be α′ phase Fe8N. The Fe8N phase composition is a chemically ordered Fe 16 The chemically disordered counterpart of the N2 phase. The Fe8N phase also has a bct crystal structure and can introduce relatively high magnetocrystalline anisotropy.

[0153] In some examples, once the iron workpiece 128 is nitrided (114), and while still being strained (112), the iron workpiece 128 may be annealed at a temperature and for a period of time to promote diffusion of nitrogen atoms into appropriate interstitial spaces in the iron lattice to form Fe 16 N2(16). Fig.15 The annealing process used in may be similar or substantially the same as that used in Figure 1 , Fig. 9 , Fig.12 and Fig.14As described. For example, the post-annealing step can be performed at a temperature below about 250°C, such as about 120°C to about 214°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The post-annealing step can be performed in a nitrogen (N2) or argon (Ar) atmosphere or in a vacuum or near vacuum. The duration of the post-annealing step can be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours.

[0154] The post-annealing temperature may be based on, for example, the size of the textured iron nitride workpiece, the diffusion coefficient of nitrogen atoms in iron at the post-annealing temperature, and the Fe 16 The temperature and duration of the post-annealing step are selected based on the desired volume fraction of N2 phase domains in the textured iron nitride workpiece. Based on these factors, the temperature and duration can be selected to provide sufficient time for nitrogen atoms to diffuse into the textured iron nitride workpiece to form Fe 16 N2 magnetic domain.

[0155] Once the annealing process has been completed, the iron workpiece 128 may be cooled in a vacuum or inert atmosphere (such as argon) to reduce or prevent oxidation.

[0156] Although Fig.15 , but in some examples, the technique may include: introducing additional ferrous or non-magnetic material between the plurality of ferrous workpieces 128 (54) ( Fig. 9 and Fig.12 ) or doping the iron workpiece 128 (108) using ion implantation or cluster implantation ( Fig.14 ).

[0157] In some instances, the iron workpiece 128 may not be of sufficiently large size for a desired application. In such instances, a plurality of iron workpieces 128 (each comprising or consisting essentially of Fe 16 N2 phase composition) and the plurality of iron workpieces 128 may be sintered together to form a larger 16 The permanent magnet (36) is composed of N2 phase. Figure 7 , Fig. 8A and Figure 8B As described, the sintering pressure, temperature, and duration may be selected to mechanically bond the workpieces while maintaining the crystal structure of the textured iron nitride workpiece (e.g., as comprising Fe 16N2 phase magnetic domain). Therefore, in some examples, the sintering step can be performed at a relatively low temperature. For example, the sintering temperature can be less than about 250°C, such as about 120°C to about 250°C, about 150°C to about 250°C, about 120°C to about 200°C, about 150°C to about 200°C, or about 150°C. The sintering pressure can be, for example, about 0.2GPa to about 10GPa. The sintering time can be at least about 5 hours, such as at least about 20 hours, or about 5 hours to about 100 hours, or about 20 hours to about 100 hours, or about 40 hours. The sintering time, temperature and pressure can be affected by the material in the workpiece or powder including iron or non-magnetic material.

[0158] After sintering the textured iron nitride workpiece with iron or non-magnetic material, a bulk magnetic material (e.g., a bulk permanent magnet) can be formed. The bulk magnetic material may include both Fe8N and Fe 16 N2 and the domain wall pinning sites provided by the iron or non-magnetic material. In this way, the bulk magnetic material can have the desired high energy product, which can approach that of pure Fe 16 Energy product of N2 (about 134MGOe).

[0159] Clause 1: A bulk permanent magnetic material comprising: about 5 volume % to about 40 volume % of Fe 16 N2 phase magnetic domains; a plurality of non-magnetic elements or compounds forming a magnetic domain wall pinning site; and a remainder of soft magnetic material, wherein at least some of the soft magnetic material is magnetically coupled to the Fe by exchange spring coupling. 16 N2 phase magnetic domain.

[0160] Item 2: The bulk permanent magnetic material of Item 1, comprising about 5 volume % to 20 volume % of Fe 16 N2 phase magnetic domain.

[0161] Item 3: The bulk permanent magnetic material of Item 1, comprising about 10 volume % to about 15 volume % of Fe 16 N2 phase magnetic domain.

[0162] Item 4: The bulk permanent magnetic material of any one of Items 1 to 3, wherein the Fe 16 The N2 phase magnetic domains are distributed throughout the volume of the bulk permanent magnetic material.

[0163] Item 5: The bulk permanent magnetic material of any one of items 1-4, wherein the plurality of non-magnetic elements or compounds comprises elements or compounds selected from the group consisting of Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3 or a combination thereof.

[0164] Clause 6: The bulk permanent magnetic material of any one of clauses 1-5, wherein the soft magnetic material is selected from the group consisting of Fe8N, Fe4N, Fe, FeCo and combinations thereof.

[0165] Clause 7: The bulk permanent magnetic material of any one of clauses 1-5, wherein the soft magnetic material comprises Fe8N.

[0166] Clause 8: The bulk permanent magnet material of any one of clauses 1-7, wherein the bulk permanent magnet comprises a plurality of sintered iron nitride pieces, each iron nitride piece comprising from about 5 volume % to about 40 volume % Fe 16 N2 phase magnetic domain.

[0167] Clause 9: The bulk permanent magnetic material of any one of clauses 1-8, wherein the smallest dimension of the bulk permanent magnetic material is greater than about 100 nanometers.

[0168] Clause 10: The bulk permanent magnetic material of Clause 9, wherein the smallest dimension is greater than about 1 micron.

[0169] Clause 11: The bulk permanent magnetic material of clause 10, wherein said smallest dimension is greater than about 100 microns.

[0170] Clause 12: The bulk permanent magnetic material of any of Clauses 1-11, wherein the magnetic material has an energy product greater than about 10 MGOe.

[0171] Clause 13: The bulk permanent magnetic material of clause 12, wherein the magnetic material has an energy product greater than about 30 MGOe.

[0172] Clause 14: The bulk permanent magnetic material of clause 13, wherein the magnetic material has an energy product greater than about 60 MGOe.

[0173] Clause 15: The bulk permanent magnetic material of clause 14, wherein the magnetic material has an energy product greater than about 100 MGOe.

[0174] Clause 16: The bulk permanent magnetic material of clause 12, wherein the magnetic material has an energy product of about 60 MGOe to about 135 MGOe.

[0175] Clause 17: The bulk permanent magnetic material of any of clauses 1-16, wherein the material is crystallographically coherent in nature.

[0176] Item 18: A method comprising: implanting N+ ions into an iron workpiece using ion implantation to form an iron nitride workpiece; pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate; and post-annealing the iron nitride workpiece to form Fe in the iron nitride workpiece. 16 N2 phase magnetic domain.

[0177] Clause 19: The method of clause 18, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises accelerating the N+ ions to an energy less than about 180 keV.

[0178] Clause 20: The method of clause 19, wherein accelerating the N+ ions to an energy of less than about 180 keV comprises accelerating the N+ ions to an energy of about 100 keV.

[0179] Clause 21: The method of any of Clauses 18-20, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece at a rate of about 2 x 10 16 / cm 2 About 1x 10 17 / cm 2 The injection amount provides N+ ions.

[0180] Clause 22: The method of any of Clauses 18-20, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece at a rate of about 8 x 10 16 / cm 2 The injection amount provides N+ ions.

[0181] Clause 23: The method of any of Clauses 18-22, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises providing sufficient N+ ions to form an average nitrogen concentration of about 8 atomic % to about 15 atomic % in the ferrous iron.

[0182] Clause 24: The method of any of Clauses 18-22, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises providing sufficient N+ ions to form an average nitrogen concentration of about 12.5 atomic % in the iron workpiece.

[0183] Clause 25: The method of any of Clauses 18-24, wherein prior to implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece, the iron workpiece defines a thickness of about 500 nanometers to about 1 millimeter.

[0184] Clause 26: The method of clause 25, wherein prior to implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece, the iron workpiece defines a thickness of approximately 500 nanometers.

[0185] Clause 27: The method of any of Clauses 18-26, wherein the ferrous workpiece comprises a plurality of ferrous crystals, and wherein a major surface of the ferrous workpiece is substantially parallel to (110) surfaces of all or substantially all of the ferrous crystals.

[0186] Clause 28: The method of any of Clauses 18-27, wherein the substrate comprises silicon or gallium arsenide.

[0187] Clause 29: The method of clause 28, wherein the substrate comprises a single crystal silicon substrate having a (111) major surface.

[0188] Clause 30: The method of clause 29, wherein pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate comprises pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a (111) major surface of a single crystal silicon substrate.

[0189] Clause 31: The method of any of Clauses 18-30, wherein pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate comprises applying an external force of about 0.2 GPa to about 10 GPa between the iron nitride workpiece and the substrate.

[0190] Clause 32: The method of any of Clauses 18-31, wherein pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate comprises heating the iron nitride workpiece and the substrate to a temperature of about 450°C to about 550°C for about 30 minutes to about 4 hours.

[0191] Clause 33: The method of clause 32, wherein pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate comprises heating the iron nitride workpiece and the substrate to a temperature of about 500°C for about 30 minutes to about 1 hour.

[0192] Clause 34: The method of clause 32 or 33, wherein pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate comprises pre-annealing the iron nitride workpiece in an atmosphere comprising nitrogen and argon.

[0193] Clause 35: The method of clause 34, wherein pre-annealing the iron nitride workpiece to attach the iron nitride workpiece to a substrate comprises pre-annealing the iron nitride workpiece in an atmosphere comprising approximately 10 vol % nitrogen, approximately 86 vol % argon, and approximately 4 vol % hydrogen.

[0194] Clause 36: The method of any of clauses 18-35, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains include heating the iron nitride workpiece and the substrate to a temperature of about 120° C. to about 250° C. for at least about 5 hours.

[0195] Clause 37: The method of any of clauses 18-35, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains include heating the iron nitride workpiece and the substrate to a temperature of about 120° C. to about 200° C. for about 20 hours to about 100 hours.

[0196] Clause 38: The method of any of clauses 18-35, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains are included by heating the iron nitride workpiece and the substrate to a temperature of about 150° C. for about 20 hours to about 40 hours.

[0197] Clause 39: The method of any of clauses 18-38, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains include about 5 volume % to about 40 volume % of Fe in the iron nitride workpiece. 16 N2 phase magnetic domain.

[0198] Clause 40: The method of any of clauses 18-38, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains contain about 10 volume % to about 20 volume % of Fe in the iron nitride workpiece. 16 N2 phase magnetic domain.

[0199] Clause 41: The method of any of clauses 18-38, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains contain about 10 volume % to about 15 volume % of Fe in the iron nitride workpiece. 16 N2 phase magnetic domain.

[0200] Clause 42: The method of any of clauses 18-41, wherein the iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domains contain Fe2+, which are distributed throughout the volume of the iron nitride workpiece. 16 N2.

[0201] Item 43: A method, comprising: forming a plurality of workpieces of an iron nitride material, each of the plurality of workpieces comprising about 5 volume % to about 40 volume % Fe 16 N2 phase magnetic domain; introducing additional iron or non-magnetic material between the plurality of workpieces or in at least one of the plurality of workpieces of iron nitride material; and sintering the plurality of workpieces of iron nitride together to form a composite material including about 5 volume % to about 40 volume % Fe 16 Bulk magnet of iron nitride with N2 phase magnetic domain.

[0202] Clause 44: The method of clause 43, wherein forming the plurality of workpieces of iron nitride material comprises: implanting N+ ions into the textured iron workpiece using ion implantation to form a textured iron nitride workpiece; and post-annealing the textured iron nitride workpiece to form Fe in the textured iron nitride workpiece. 16 N2 phase magnetic domain.

[0203] Clause 45: The method of clause 44, further comprising forming the textured iron workpiece using rapid strip casting.

[0204] Clause 46: The method of clause 44 or 45, wherein the textured ferrous workpiece defines a thickness of about 1 micrometer to about 10 millimeters.

[0205] Clause 47: The method of clause 44 or 45, wherein the textured ferrous workpiece defines a thickness of about 5 microns to about 1 millimeter.

[0206] Clause 48: The method of any of Clauses 44-47, wherein the textured ferrous workpiece comprises a (100) or (110) crystal structure.

[0207] Clause 49: The method of any of Clauses 44-48, wherein implanting N+ ions into the textured workpiece using ion implantation to form a textured iron nitride workpiece comprises accelerating the N+ ions to an energy less than about 180 keV.

[0208] Clause 50: The method of any of clauses 44-48, wherein accelerating the N+ ions to an energy of less than about 180 keV comprises accelerating the N+ ions to an energy of about 100 keV.

[0209] Clause 51: The method of any of Clauses 44-50, wherein implanting N+ ions into the textured workpiece using ion implantation to form the textured iron nitride workpiece comprises implanting N+ ions into the textured workpiece using ion implantation to form the textured iron nitride workpiece at a rate of about 2x10 16 / cm 2 About 1x 10 17 / cm 2 The injection amount provides N+ ions.

[0210] Clause 52: The method of any of clauses 44-50, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece at a rate of about 8 x 10 16 / cm 2 The injection amount provides N+ ions.

[0211] Clause 53: The method of any of clauses 44-52, wherein implanting N+ ions into the textured workpiece using ion implantation to form a textured iron nitride workpiece comprises providing sufficient N+ ions to form an average nitrogen concentration of about 8 atomic % to about 15 atomic % in the textured iron nitride workpiece.

[0212] Clause 54: The method of any of Clauses 44-52, wherein implanting N+ ions into the textured workpiece using ion implantation to form a textured iron nitride workpiece comprises providing sufficient N+ ions to form an average nitrogen concentration of about 12.5 atomic % in the textured iron nitride workpiece.

[0213] Clause 55: The method of clause 43, wherein forming the plurality of workpieces of iron nitride material comprises: mixing a nitrogen source in molten iron; rapidly belt casting the molten iron to form a textured iron nitride workpiece; and post annealing the textured iron nitride workpiece to form Fe in the textured iron nitride workpiece. 16 N2 phase magnetic domain.

[0214] Clause 56: The method of clause 55, wherein mixing nitrogen into the molten iron comprises: mixing the nitrogen source into the molten iron to produce a nitrogen atomic concentration of about 8 atomic % to about 15 atomic % in the molten iron.

[0215] Clause 57: The method of clause 55, wherein mixing nitrogen into the molten iron comprises: mixing the nitrogen source into the molten iron to produce a nitrogen atomic concentration of about 12.5 atomic % in the molten iron.

[0216] Clause 58: The method of any of clauses 55-57, wherein the nitrogen source comprises at least one of ammonia, ammonium azide, or urea.

[0217] Clause 59: The method of any of Clauses 55-58, wherein the textured iron nitride workpiece comprises a (100) or (110) crystal structure.

[0218] Clause 60: The method of any of Clauses 55-59, wherein the textured iron nitride workpiece defines a dimension of about 1 micron to about 10 millimeters.

[0219] Clause 61: The method of any of Clauses 55-59, wherein the textured iron nitride workpiece defines a thickness of about 5 microns to about 1 millimeter.

[0220] Clause 62: The method of any of clauses 43-61, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domain comprises applying a strain of about 0.1% to about 7% on the textured iron nitride workpiece; and while applying the strain on the textured iron nitride workpiece, the textured iron nitride workpiece is heated to a temperature of about 120° C. to about 250° C. for at least about 5 hours.

[0221] Clause 63: The method of clause 62, wherein heating the textured iron nitride workpiece to a temperature of about 120°C to about 250°C for at least about 5 hours comprises heating the textured iron nitride workpiece to a temperature of about 120°C to about 200°C for about 20 hours to about 100 hours.

[0222] Clause 64: The method of clause 62, wherein heating the textured iron nitride workpiece to a temperature of about 120°C to about 250°C for at least about 5 hours comprises heating the textured iron nitride workpiece to a temperature of about 150°C for about 20 hours to about 40 hours.

[0223] Clause 65: The method of any of clauses 44-64, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 N2 phase magnetic domains comprise about 5 volume % to about 40 volume % of Fe in the textured iron nitride workpiece. 16 N2 phase magnetic domain.

[0224] Clause 66: The method of any of clauses 44-64, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 N2 phase magnetic domains contain about 5 volume % to about 20 volume % of Fe in the textured iron nitride workpiece. 16 N2 phase magnetic domain.

[0225] Clause 67: The method of any of clauses 44-64, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 N2 phase magnetic domains comprise about 10 volume % to about 15 volume % of Fe in the textured iron nitride workpiece. 16 N2 phase magnetic domain.

[0226] Clause 68: The method of any of clauses 44-67, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 N2 phase magnetic domains contain Fe2+, which are distributed throughout the volume of the textured iron nitride workpiece. 16 N2.

[0227] Clause 69: The method of any of clauses 43-68, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or into at least one of the plurality of workpieces of iron nitride material comprises using ion implantation to implant non-magnetic ions into at least one of the plurality of workpieces of iron nitride material.

[0228] Clause 70: The method of any of clauses 43-69, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or into at least one of the plurality of workpieces of iron nitride material comprises implanting a non-magnetic compound into at least one of the plurality of workpieces of iron nitride material using cluster implantation.

[0229] Item 71: The method of any of items 43-70, wherein introducing additional iron or non-magnetic material between the multiple workpieces or into at least one of the multiple workpieces of iron nitride material includes introducing a workpiece of iron or non-magnetic material between a first workpiece and a second workpiece of the multiple workpieces of iron nitride material.

[0230] Item 72: The method of any of items 43-71, wherein introducing additional iron or non-magnetic material between the multiple workpieces or into at least one of the multiple workpieces of iron nitride material includes introducing a powder comprising at least one of the iron or non-magnetic material between a first workpiece and a second workpiece of the multiple workpieces of iron nitride material.

[0231] Item 73: The method of any of items 43-71, wherein the ferrous or non-magnetic material is selected from the group consisting of Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3, or a combination thereof.

[0232] Clause 74: The method of any of clauses 43-73, wherein a plurality of iron nitride workpieces are sintered together to form a composite having from about 5 volume % to about 40 volume % Fe 16 The step of heating the plurality of workpieces comprising the iron nitride material to a temperature below about 250° C. for at least about 5 hours comprises heating the plurality of workpieces comprising the iron nitride material to a temperature below about 250° C. for at least about 5 hours.

[0233] Clause 75: The method of any of clauses 43-73, wherein a plurality of iron nitride workpieces are sintered together to form a composite having about 5 volume % to about 40 volume % Fe 16 Forming an iron nitride bulk magnet having N2 phase magnetic domains includes heating the plurality of iron nitride workpieces to a temperature below about 250° C. for at least about 5 hours while applying a pressure of about 0.2 GPa to about 10 GPa to the plurality of iron nitride workpieces.

[0234] Clause 76: The method of any of clauses 43-73, wherein a plurality of iron nitride workpieces are sintered together to form a sheet comprising about 5 volume % to about 40 volume % Fe 16 The method of forming a bulk magnet of iron nitride having N2 phase magnetic domains comprises heating the plurality of iron nitride workpieces to a temperature of about 120° C. to about 200° C. for about 20 hours to about 100 hours while applying a pressure of about 0.2 GPa to about 10 GPa to the plurality of iron nitride workpieces.

[0235] Item 77: A method comprising: forming a plurality of textured iron nitride workpieces by implanting N+ ions into the textured iron workpiece using ion implantation to form a textured iron nitride workpiece comprising about 8 atomic % to about 15 atomic % N+ ions; and post-annealing the textured iron nitride workpieces to form a Fe volume fraction of about 5 volume % to about 40 volume % in the textured iron nitride workpieces. 16 N2 phase magnetic domain, the remainder is a soft magnetic material including Fe8N, wherein the Fe 16 at least some of the N2 phase magnetic domains are magnetically coupled to at least one of the Fe8N magnetic domains through exchange spring coupling; introducing a non-magnetic material between a first workpiece of the plurality of workpieces and a second workpiece of the plurality of workpieces or within at least one of the plurality of iron nitride workpieces; and sintering the plurality of iron nitride workpieces together to form a composite material comprising about 5 volume % to about 40 volume % Fe8N. 16 A bulk magnet of iron nitride with N2 phase magnetic domains, wherein the non-magnetic material forms a magnetic domain wall pinning site in the bulk magnet.

[0236] Clause 78: The method of clause 77, further comprising forming the textured iron workpiece using rapid strip casting.

[0237] Clause 79: The method of clause 77 or 78, wherein the textured ferrous workpiece defines a thickness of about 1 micrometer to about 10 millimeters.

[0238] Clause 80: The method of clause 77 or 78, wherein the textured ferrous workpiece comprises a (100) or (110) crystal structure.

[0239] Clause 81: The method of any of clauses 77-80, wherein implanting N+ ions into the textured workpiece using ion implantation to form the textured iron nitride sheet comprises accelerating the N+ ions to an energy of about 100 keV.

[0240] Clause 82: The method of any of clauses 77-81, wherein implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece comprises implanting N+ ions into the iron workpiece using ion implantation to form the iron nitride workpiece at a rate of about 8 x 10 16 / cm 2 The injection amount provides N+ ions.

[0241] Clause 83: The method of any of clauses 77-82, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domain comprises: applying a strain of about 0.1% to about 7% on the textured iron nitride workpiece; and heating the textured iron nitride workpiece to a temperature of about 120° C. to about 250° C. for at least about 5 hours while applying the strain on the textured iron nitride workpiece.

[0242] Clause 84: The method of clause 83, wherein heating the textured iron nitride workpiece to a temperature of about 120°C to about 250°C for at least about 5 hours comprises heating the textured iron nitride workpiece to a temperature of about 120°C to about 200°C for about 20 hours to about 100 hours.

[0243] Clause 85: The method of any of clauses 77-84, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 N2 phase magnetic domains contain Fe2+, which are distributed throughout the volume of the textured iron nitride workpiece. 16 N2.

[0244] Clause 86: The method of any of clauses 77-85, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or into at least one of the plurality of workpieces of iron nitride material comprises implanting non-magnetic ions into at least one of the plurality of workpieces of iron nitride material using ion implantation.

[0245] Clause 87: The method of any of clauses 77-86, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or into at least one of the plurality of workpieces of iron nitride material comprises introducing a non-magnetic compound into at least one of the plurality of workpieces of iron nitride material using cluster implantation.

[0246] Item 88: The method of any of items 77-87, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or within at least one of the plurality of workpieces of iron nitride material comprises introducing a workpiece of iron or non-magnetic material between a first workpiece and a second workpiece of the plurality of workpieces of iron nitride material.

[0247] Item 89: The method of any of items 77-88, wherein introducing additional iron or non-magnetic material between the multiple workpieces or into at least one of the multiple workpieces of iron nitride material includes introducing a powder comprising at least one of the iron or non-magnetic material between a first workpiece and a second workpiece of the multiple workpieces of iron nitride material.

[0248] Item 90: The method of any of items 77-89, wherein the ferrous or non-magnetic material is selected from the group consisting of Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3, or a combination thereof.

[0249] Clause 91: The method of any of clauses 77-90, wherein the plurality of iron nitride workpieces are sintered together to form a sheet comprising about 5 volume % to about 20 volume % Fe 16The method of forming a bulk magnet of iron nitride with N2 phase magnetic domains includes heating the plurality of iron nitride workpieces to a temperature of about 120° C. to about 200° C. for about 20 hours to about 100 hours while applying a pressure of about 0.2 GPa to about 10 GPa.

[0250] Item 92: A method comprising: forming a plurality of textured iron nitride workpieces by mixing a nitrogen source in molten iron to produce a nitrogen source concentration in the molten iron of about 8 atomic % to about 15 atomic %, rapidly tape casting the molten iron to form the textured iron nitride workpieces, and post annealing the textured iron nitride workpieces to form a volume fraction of about 5 volume % to about 40 volume % Fe in the textured iron nitride workpieces. 16 N2 phase magnetic domain, the remainder is a soft magnetic material containing Fe8N, wherein the Fe 16 At least some of the N2 phase magnetic domains are magnetically coupled to at least one of the Fe8N magnetic domains through exchange spring coupling; introducing a non-magnetic material between a first workpiece of the plurality of workpieces and a second workpiece of the plurality of workpieces or within at least one of the plurality of iron nitride workpieces; and sintering the plurality of iron nitride workpieces together to form a composite material having about 5 volume % to about 40 volume % Fe 16 A bulk magnet of iron nitride with N2 phase magnetic domains, wherein the non-magnetic material forms a magnetic domain wall pinning site in the bulk magnet.

[0251] Item 93: The method of item 92, wherein the nitrogen source comprises at least one of ammonia, ammonium azide, or urea.

[0252] Clause 94: The method of clause 92 or 93, wherein the textured iron nitride workpiece comprises a (100) or (110) crystal structure.

[0253] Clause 95: The method of any of Clauses 92-94, wherein the textured iron nitride workpiece defines a thickness of about 1 micrometer to about 10 millimeters.

[0254] Clause 96: The method of any of clauses 92-95, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 The N2 phase magnetic domain comprises: applying a strain of about 0.1% to about 7% on the textured iron nitride workpiece; and heating the textured iron nitride workpiece to a temperature of about 120° C. to about 250° C. for at least about 5 hours while applying the strain on the textured iron nitride workpiece.

[0255] Item 97: The method of item 96, wherein heating the textured iron nitride workpiece to a temperature of about 120°C to about 250°C for at least about 5 hours comprises heating the textured iron nitride workpiece to a temperature of about 120°C to about 200°C for about 20 hours to about 100 hours.

[0256] Clause 98: The method of any of clauses 92-97, wherein the textured iron nitride workpiece is post-annealed to form Fe 16 N2 phase magnetic domains contain Fe2+, which are distributed throughout the volume of the textured iron nitride workpiece. 16 N2.

[0257] Clause 99: The method of any of clauses 92-98, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or into at least one of the plurality of workpieces of iron nitride material comprises implanting non-magnetic ions into at least one of the plurality of workpieces of iron nitride material using ion implantation.

[0258] Clause 100: The method of any of clauses 92-99, wherein introducing additional iron or non-magnetic material between the plurality of workpieces or within at least one of the plurality of workpieces of iron nitride material comprises introducing a non-magnetic compound within at least one of the plurality of workpieces of iron nitride material using cluster implantation.

[0259] Item 101: The method of any of items 92-100, wherein introducing additional ferrous or non-magnetic material between the plurality of workpieces or within at least one of the plurality of workpieces of iron nitride material comprises introducing a workpiece of ferrous or non-magnetic material between a first workpiece and a second workpiece of the plurality of workpieces of iron nitride material.

[0260] Item 102: The method of any of items 92-101, wherein introducing additional iron or non-magnetic material between the multiple workpieces or in at least one of the multiple workpieces of iron nitride material includes introducing a powder comprising at least one of the iron or non-magnetic material between a first workpiece and a second workpiece of the multiple workpieces of iron nitride material.

[0261] Item 103: The method of any of items 92-102, wherein the ferrous or non-magnetic material is selected from the group consisting of Al, Cu, Ti, Mn, Zr, Ta, B, C, Ni, Ru, SiO2, Al2O3, or a combination thereof.

[0262] Clause 104: The method of any of clauses 92-103, wherein a plurality of iron nitride workpieces are sintered together to form a composite material comprising about 5 volume % to about 20 volume % Fe 16The method of forming a bulk magnet of iron nitride with N2 phase magnetic domains includes heating the plurality of iron nitride workpieces to a temperature of about 120° C. to about 200° C. for about 20 hours to about 100 hours while applying a pressure of about 0.2 GPa to about 10 GPa to the plurality of iron nitride workpieces.

[0263] Item 105: A method for performing a method described herein for forming a 16 A system of technology for magnetic materials with N2 phase magnetic domains.

[0264] Example

[0265] Example 1

[0266] Fig.19 Graph showing Auger measurements of N+ ion concentration versus depth in an iron foil after ion implantation and before annealing the iron nitride foil. The iron foil had a thickness of about 500 nm before N+ ion implantation. The N+ ions were accelerated to 100 keV for implantation into the iron film. Approximately 8x10 16 / cm 2 N+ ions were implanted into the iron foil using an N+ ion dosing ratio of N+ ions. Auger electron spectroscopy (AES) was performed using a Physical Electronics Industries (PHI) 545 scanning Auger microprobe available from Physical Electronics, Inc., Chanhassen, Minnesota at a milling source using an Ar + The measurements are performed. Figure 2 As predicted by the relationship shown in , the peak position of N+ ion concentration is about or 100nm. In addition, N+ ion implantation Other nearby depths.

[0267] Example 2

[0268] Fig. 20 Figure 1 is a scatter plot showing the nitrogen concentration as a function of depth in an iron foil after annealing at different nitrogen fluencies. Before N+ ion implantation, the iron foil had a thickness of about 500 nm. The N+ ions were accelerated to 100 keV to be implanted into the iron foil. Approximately 2 x 10 16 / cm 2 , 5x 10 16 / cm 2 , 8x 10 16 / cm 2 and 1x 10 17 / cm 2The N+ ions are implanted into the iron foil at a dose of N+ ions. After the ion implantation, the iron nitride foil is attached to a (111) silicon substrate and subjected to a pre-annealing treatment at about 500° C. for about 0.5 hours in a 4% H2+10% N2+86% Ar atmosphere. The iron nitride foil is then subjected to a post-annealing treatment at about 150° C. in a vacuum for about 40 hours.

[0269] like Fig. 20 As shown, the thickness of the iron nitride foil after the post-annealing step is about 450 nm. It is believed that the loss of 50 nm in thickness is due to the loss of iron during the ion bombardment process and the cleaning during the post-annealing step. Fig. 20 As shown, for each nitrogen fluency, the concentration of nitrogen in the foil after the post-annealing step is substantially the same throughout the foil. 16 / cm 2 The nitrogen concentration of the N+ ion fluency (triangle pointing upward) is about 12.5 atomic % to about 10 atomic %, close to Fe 16 Stoichiometric ratio of Fe:N in N2.

[0270] Example 3

[0271] Fig.21A and Fig.21B 1 is a hysteresis loop of magnetization versus coercivity for an example of an iron nitride foil prepared using ion implantation. Before N+ ion implantation, the iron foil had a thickness of about 500 nm. The N+ ions were accelerated to 100 keV to be implanted into the iron film. Approximately 8 x 10 16 / cm 2 The N+ ion implantation of N+ ions implants N+ ions into the iron foil. After the ion implantation, the iron nitride foil is attached to a (111) silicon substrate and subjected to a pre-annealing treatment at about 500° C. for about 0.5 hours in a 4% H2+10% N2+86% Ar atmosphere. The iron nitride foil is then subjected to a post-annealing treatment at about 150° C. for about 40 hours in a vacuum.

[0272] Fig.21A The hysteresis loop of iron nitride foil at a temperature of about 5K is shown. Fig.21A As shown in FIG. 1 , the pre-annealing and post-annealing treatments introduce an increase in saturation magnetization from about 2.0 Tesla (T) to about 2.45 T. The pre-annealing and post-annealing treatments also increase the coercivity (H s ) increases from about 0 to about 3.2 kOe.

[0273] Fig.21B The hysteresis loop of the iron nitride foil at a temperature of about 300 K is shown. Fig.21BAs shown, the pre-annealing and post-annealing treatments result in an increase in saturation magnetization from about 2.0 T to about 2.12 T. The pre-annealing and post-annealing treatments also increase the coercivity (H s ) increases from about 0 to about 26 Oe. The difference in performance between the foil tested at 5K and the foil tested at about 300K is believed to be due to defects in the material that affect the results at higher temperatures, but the effect is reduced at lower temperatures. Therefore, the results at 5K are believed to represent the desired properties of some iron nitride films prepared using the present technique.

[0274] Example 4

[0275] A pure (110) iron foil with a thickness of about 500 nm was positioned on a mirror-polished (111) Si. Nitrogen ions N+ were accelerated to 100 keV and vertically and at room temperature at 2 x 10 16 / cm 2 , 5x10 16 / cm 2 , 8x 10 16 / cm 2 and 1x 10 17 / cm 2 The foils are implanted with a dose of 100 Å to 200 Å. After the ion implantation, a two-step annealing process is applied to the implanted foils. The first step is a pre-annealing at 500° C. for 0.5 hours in an atmosphere of nitrogen and argon. After this pre-annealing step, a post-annealing treatment is performed at about 150° C. in vacuum for about 40 hours.

[0276] The samples were exposed to the same implant energy but different nitrogen fluencies. Fig. 22 is a line graph showing an example of nitrogen depth profile in an iron foil before annealing. The nitrogen depth profile was measured by Auger Electron Spectroscopy (AES) with Ar+ as the deep milling source.

[0277] The extent of nitrogen implantation in the foil is determined by the implantation energy. Fig. 22 As shown, the four samples with different nitrogen fluency have the same implantation range (about 160 nm) and the same peak position (about 100 nm), which is consistent with the simulation results by SRIM.

[0278] Example 5

[0279] A pure (110) iron foil with a thickness of about 500 nm was positioned on a mirror-polished (111) Si. Nitrogen ions N+ were accelerated to 100 keV and vertically and at room temperature at 2 x 10 16 / cm 2 , 5x10 16 / cm 2 , 8x 1016 / cm 2 and 1x 10 17 / cm 2 The foils were implanted with a dose of 100 Å to 200 Å. After the ion implantation, a two-step annealing process was applied to the implanted foils. The first step was a pre-annealing at 500° C. for 0.5 hours in an atmosphere of nitrogen and argon. After the pre-annealing step, a post-annealing treatment was performed at about 150° C. in vacuum for about 40 hours.

[0280] Fig.23 The figure is a scatter plot showing the variation of nitrogen concentration with depth in iron foil after annealing at different nitrogen fluencies. Fig.23 It is shown that the nitrogen concentration in the annealed foil is essentially uniform for each nitrogen fluency. 16 / cm 2 The nitrogen concentration distribution of iron nitride reaches 11 atomic %, close to Fe 16 The stoichiometric ratio of nitrogen in N2.

[0281] Example 6

[0282] A pure (110) iron foil with a thickness of about 500 nm was positioned on a mirror-polished (111) Si. Nitrogen ions N+ were accelerated to 100 keV and vertically and at room temperature at 2 x 10 16 / cm 2 , 5x10 16 / cm 2 , 8x 10 16 / cm 2 and 1x 10 17 / cm 2 The foils are implanted with a dose of 100 Å to 200 Å. After the ion implantation, a two-step annealing process is applied to the implanted foils. The first step is a pre-annealing at 500° C. for about 0.5 hours in an atmosphere of nitrogen and argon. After this pre-annealing step, a post-annealing treatment is performed at about 150° C. in vacuum for about 40 hours.

[0283] The crystal structure of the foil samples was characterized using a Siemens D5005 X-ray diffractometer (XRD) with a Cu Ka radiation source. Fig.24 The use of 8x 10 16 / cm 2 XRD patterns of the foil sample formed by nitrogen ion implantation before and after annealing. For the spectrum before annealing, in addition to the Si(111) peak of the silicon substrate, a bcc Fe(110) peak also appears. After annealing, the Fe 16 N2(330)( Fig.24 The (not shown) and (220) peaks indicate that part of the bcc Fe has been converted to Fe 16N2 phase. Fig.24 Also shown is the reduction in the intensity of the Fe8N (330) peak after annealing.

[0284] Example 7

[0285] A pure (110) iron foil with a thickness of about 500 nm was positioned on a mirror-polished (111) Si. Nitrogen ions N+ were accelerated to 100 keV and vertically and at room temperature at 8 x 10 16 / cm 2 A dose of 500 Å was implanted into these foils. After the ion implantation, a two-step annealing process was applied to the implanted foils. The first step was a pre-annealing at 500° C. in a nitrogen and argon atmosphere for 0.5 hours. After this pre-annealing step, a post-annealing treatment was performed at about 150° C. in vacuum for about 40 hours.

[0286] Fig.25 : The hysteresis loop of magnetization intensity versus coercivity for an example of an iron nitride foil prepared using ion implantation. Before ion implantation ( Fig.25 The magnetic properties of the iron foil are as expected for an iron single crystal, with the remanent magnetization being almost equal to the saturation magnetization (about 2.02 T at room temperature). This indicates an easy axis located in the in-plane direction. After the ion implantation and pre-annealing steps, the saturation magnetization increased by about 7% compared to the iron foil. After the post-annealing, the saturation magnetization increased by about 15% compared to the iron foil. After the ion implantation, pre-annealing, and post-annealing, the saturation magnetic field (H s ) increased to about 5.3 kOe, indicating that due to Fe 16 The bct structure in N2 leads to perpendicular magnetic anisotropy.

[0287] Example 8

[0288] A pure (110) iron foil with a thickness of about 500 nm was positioned on a mirror-polished (111) Si. Nitrogen ions N+ were accelerated to 100 keV and vertically and at room temperature at 2 x 10 16 / cm 2 , 5x10 16 / cm 2 , 8x 10 16 / cm 2 and 1x 10 17 / cm 2 The ion implantation is followed by a two-step annealing process on the implanted foils. The first step is a pre-annealing at 500°C in a nitrogen and argon atmosphere for about 0.5 hours. After the pre-annealing, a post-annealing process is performed at about 150°C in a vacuum for about 40 hours.

[0289] To determine the chemical state of nitrogen in the FeN foil before and after annealing, X-ray photoelectron spectroscopy (XPS) was used to measure the nitrogen binding energy. Fig.26 Included are two line graphs showing the binding energy of nitrogen before and after the annealing process. 1s The binding energy of N is about 401 eV, indicating a positively charged state compared to the neutral state. This indicates that nitrogen maintains its ionized (N+) state after implantation. After annealing, the binding energy of nitrogen moves to about 397 eV, corresponding to a negatively charged state. This means that, after annealing, nitrogen has bound to iron.

[0290] Example 9

[0291] As compared to Figure 15-18 As described, the iron nitride sample was prepared by exposing the strained iron sample to urea using the cold crucible technique. The iron sample was heated to a temperature of about 660°C for about 4 hours while exposed to urea (1 gram of urea per gram of iron), and then the iron sample was water cooled.

[0292] The iron samples were then cut into wires and Fig.11 The three wires were strained to different lengths and the strain was determined using a strain gauge. The first sample was subjected to a tensile force of about 830 Newtons (N), which produced a strain of about 2.5%. The second sample was subjected to a tensile force of about 1328N, which produced a strain of about 4%. The third sample was subjected to a tensile force of about 1660N, which produced a strain of about 5%. Each sample was annealed at about 150°C for about 20 hours while being strained by a specified amount.

[0293] The crystal structures of the three samples were characterized using a Siemens D5005 X-ray diffractometer (XRD) with a Cu Kα radiation source. Figure 27-Figure 29 Shown are XRD patterns of three iron nitride samples collected. Fig. 27 Results are shown for a sample strained to 2.5%. The XRD pattern includes Fe 16 N2(002),Fe 16 N2(301) and Fe 16 N2(004) as well as peaks of other iron nitride (Fe4N(111)), iron (Fe(110), Fe(200), and Fe(211)) and iron oxide (Fe3O4) phases.

[0294] Fig.28 Results are shown for a sample strained to 4%. The XRD pattern includes Fe 16 N2(002),Fe 16 N2(301) and Fe 16N2(004) as well as peaks of other iron nitride (Fe4N(111)), iron (Fe(110), Fe(200), and Fe(211)) and iron oxide (Fe3O4) phases.

[0295] Fig.29 Results are shown for samples strained to 5%. The XRD pattern includes Fe 16 N2(002) and Fe 16 N2(004) as well as peaks of other iron nitride (Fe4N(111)) and iron (Fe(200) and Fe(211)) phases.

[0296] Figure 30-Figure 32 are hysteresis loops of magnetization versus coercivity for examples of iron nitride wires exposed to different strains (2.5%, 4% and 5%) during annealing. The hysteresis loops were measured at room temperature. Fig.30 It is shown that after annealing, the sample subjected to about 2.5% strain has a saturation magnetization (M) of about 138 emu / g. s ) and a coercivity of about 660Oe (H c ). Fig.31 It is shown that after annealing, the sample subjected to about 4% strain has a saturation magnetization (Ms) of about 165 emu / g and a coercivity (Hc) of about 750 Oe. Fig.32 It is shown that after annealing, the sample subjected to about 4% strain has a saturation magnetization (Ms) of about 170 emu / g and a coercive force (Hc) of about 800 Oe.

[0297] Example 10

[0298] A pure (110) iron foil with a thickness of 500 nm was positioned on a mirror-polished (111) Si substrate. The surfaces of the substrate and the iron foil were cleaned beforehand. The foil was directly bonded to the substrate at 450° C. for 30 minutes using a wafer bonder (SB6, Karl Suss WaferBonder) in fusion mode. Fig.33 An example infrared image showing an iron foil directly bonded to a (111) Si substrate.

[0299] The atomic ion N + accelerated to 100 keV and at room temperature at 2×10 16 / cm 2 Up to 5×10 17 / cm 2The samples were exposed to the same implantation energy but different nitrogen fluencies. Thereafter, a two-step post-annealing process was applied on the implanted foil. The first annealing step was a pre-annealing at 500°C for 30 minutes in a N2 and Ar mixed atmosphere. This pre-annealing was followed by a post-annealing at 150°C in vacuum for 40 hours.

[0300] Fig.34 A graph showing an example nitrogen depth profile of an ion implanted sample prior to two-step annealing, obtained by Auger electron spectroscopy (AES) with Ar + Measured as a source of deep milling. Fig.34 It shows that there are 2×10 16 / cm 2 , 8×10 16 / cm 2 , 1×10 17 / cm 2 and 5×10 17 / cm 2 The nitrogen distribution of the four samples before annealing is shown in Figure 1. The nitrogen implantation range in the foil is determined by the implantation energy. Figure 1 As shown, the four samples have substantially the same implantation range (about 160 nm) and substantially the same peak position (about 100 nm), which is consistent with the simulation results of SRIM.

[0301] Fig.35 is a graph showing an example nitrogen depth profile after a two-step anneal. After annealing, the nitrogen concentration in the foil is substantially uniformly dispersed throughout the depth of the foil. 17 / cm 2 The nitrogen concentration distribution of the injection is about 11 atomic %, close to Fe 16 The stoichiometric ratio of nitrogen in N2 is 5×10 17 / cm 2 In the sample with the injection, the nitrogen concentration has exceeded the maximum nitrogen solubility achievable in iron.

[0302] The crystal structure of the foil samples was characterized using a Siemens D5005 X-ray diffractometer (XRD) with a Cu Ka radiation source. Fig.36 Figure 2 is a diagram showing example XRD patterns of foil samples with different nitrogen fluency on Si(111) substrate after post-annealing. 16 / cm 2 Up to 5×10 17 / cm 2 Fe was always present under all test conditions of ion dosing. 16 N2 phase. For 2×10 16 / cm 2 and 8×1016 / cm 2 ion injection, only Fe 16 N2 phase iron nitride. For 1×10 17 / cm 2 and 5×10 17 / cm 2 For the sample with 400°C injection, the peak of ε-iron nitride (Fe4N) was also observed due to the nitrogen concentration greater than 11.1 atomic %. The FeSi(111) phase was observed at all injections, indicating the appearance of the iron silicide interface due to melt bonding at 450°C.

[0303] Fig.37 For illustration, 1×10 17 / cm 2 Figure 2. Example hysteresis loops of a sample prepared by flux injection at different stages, measured at room temperature on the foil plane using a vibrating sample magnetometer (VSM) calibrated with a standard Ni sample. The three MH loops correspond to the same sample before ion implantation, after ion implantation and pre-annealing steps, and after ion implantation and pre-annealing and post-annealing steps. For the pure iron foil between ion implantation, its magnetic properties are in good agreement with those of a Fe(110) single crystal. Its remanent magnetization value is equal to that of a Fe(110) single crystal with 4πM S The saturation magnetization value of the samples was about 2.02 T at room temperature. For the samples after ion implantation and a pre-annealing step at 500 °C for 0.5 hours, the saturation magnetization increased by about 7% to as much as 2.15 T. At the same time, the residual magnetization value after the pre-annealing step decreased and the saturation magnetic field (Hs) increased up to about 1000 Oe, indicating the presence of the Fe8N phase after the pre-annealing step.

[0304] A post-annealing step at 150 °C for 40 h greatly changes the MH loop of the sample, as shown in Fig.36 As shown, it is related to the Fe 16 N2 phase is well matched. Fig.37 As shown in Figure 2, the hard magnetic characteristics are clearly observed, and the saturation magnetic field is 5.3 kOe. This is consistent with the fact that Fe 16 The results are consistent with the presence of large magnetocrystalline anisotropy due to the body-centered tetragonal (bct) structure in N2. In addition, a 15% increase in saturation magnetization was observed in this sample, which is larger than the VSM test error. The absolute M is 2.02 T compared to 2.02 T of the control sample (starting single crystal iron foil). s The value increased to 2.32T. Fig.36 The XRD patterns shown clearly show the Fe and Fe 16 N2 mixed phase. Based on XRD patterns, Fe 16The estimated volume ratio of the N2 phase in this sample is about 35%. 16 The saturation magnetization of the N2 phase in this sample was calculated to be about 2.9 T. For this calculation, we assumed that the Fe matrix in the sample had the same saturation magnetization as before ion implantation and annealing, which is reasonable because we used the same sample before and after ion implantation.

[0305] For a 5×10 17 / cm 2 The magnetic properties of the sample with the highest flux before annealing are basically similar to those of Fig.37 However, if Fig.38 and Fig.39 As shown, the magnetic properties of the film change significantly after post-annealing, with a significant increase in coercivity and therefore also in the maximum energy product. Fig.38 For illustration, 5×10 17 / cm 2 Figure 2 shows an example hysteresis loop of a sample prepared by post-annealing. The film has a coercivity of 1910 Oe, a saturation magnetization of 245 emu / g, and an energy product (BH) of max ) is about 20MGOe. Fig.39 To show that to obtain Fig.38 The results shown in Figure 5 are a diagram of the calculated energy products of the tested membranes. Fig.39 It is shown that the maximum value of the energy product of the film is about 20 MGOe.

[0306] Fig.40 To obtain Fig.38 and Fig.39 The results are shown in the high resolution transmission electron microscopy (HRTEM) images of the tested membranes. The TEM samples were obtained by focused ion beam (FIB) (FEI TM Quanta 200 3D, available from FEI TM , Hillsboro, Oregon) by cutting and polishing the foil perpendicular to the surface. Fig.40 As shown, the sample consists of a granular structure. Subregions of the sample correspond to different crystal structures, one with a 16 N2(220) has a lattice fringe spacing of 2.022nm, and the other has a lattice fringe spacing of 1.897nm and 2.027nm corresponding to Fe4N(200) and Fe(110), respectively. Fig.41 is shown to obtain Fig.40 The results shown in Figure 5 are example images of x-ray diffraction patterns of the tested samples.

[0307] Various embodiments have been described. These and other embodiments are within the scope of the following claims.

Claims

1. A bulk ferronitride magnet, comprising: A plurality of textured iron nitride workpieces sintered together to form a bulk iron nitride magnet, the textured iron nitride workpieces being characterized by having about 5 volume % to about 40 volume % Fe 16 The volume fraction of the N2 phase magnetic domains, including the remaining volume fraction of the soft magnetic phase, where the Fe 16 At least some of the N2 phase magnetic domains are magnetically coupled to at least one phase magnetic domain in the soft magnetic phase through exchange spring coupling, and Non-magnetic materials; The non-magnetic material is disposed between two or more of the sintered textured iron nitride workpieces, or said non-magnetic material being disposed in at least one of said textured iron nitride workpieces; The non-magnetic material generates magnetic domain wall pinning sites within the bulk magnet, wherein the soft magnetic phase comprises Fe8N phase magnetic domains.

2. The bulk nitride iron magnet according to claim 1, wherein the Fe 16 The crystal texture of the N2 phase magnetic domains and the soft magnetic phase are coherent.

3. The bulk nitride iron magnet according to claim 1, wherein the Fe 16 The N2 phase magnetic domain is magnetically coupled to at least one Fe8N phase magnetic domain in the soft magnetic phase.

Citation Information

Patent Citations

  • Iron nitride permanent magnet and technique for forming iron nitride permanent magnet

    CN107919201A

  • Iron nitride permanent magnet and technique for forming iron nitride permanent magnet

    CN112164539A